A potential new sea surface temperature proxy based on isomeric highly branched isoprenoid lipid biomarkers: EZ25 - Belt, Simon T.; Smik, Lukas; Husum, Katrine; Knies, Jochen (Organic Geochemistry, 2025)
Two tri-unsaturated and isomeric (E/Z) highly branched isoprenoid (HBI) diatom lipid biomarkers were quantified in 228 water column samples collected from the English Channel, West Svalbard (Arctic), the Scotia Sea (Southern Ocean) and East Antarctica. We found that the relative amounts of the two HBIs correlate well with water temperatures taken at the time of sampling. Based on these findings and some other HBI data reported previously, we suggest that the proportion of the HBI E-isomer (termed EZ25) may serve as a new proxy for palaeo sea surface temperatures, including in the polar regions. Next steps will involve determination of EZ25 in surface and downcore sediments to ascertain whether the temperature response described herein translates well to the geological record.
Keywords: Scotiahavet; Sørishavet; biogeokjemi; biomarkører; geologi; paleontologi; polarområdene

The Maud Belt (East Antarctica) as an accretionary orogen in Rodinia: Isotopic composition, evolution and spatial variation - Wang, Cheng-Cheng; Jacobs, Joachim; Marschall, Horst R.; Hemming, Sidney; Jacques, Guillaume; Läufer, Andreas (Gondwana Research, 2025)
The Maud Belt of East Antarctica represents a late Mesoproterozoic orogen along the periphery of the Proto-Kalahari Craton, and a better understanding of its orogenic nature helps to elucidate the configuration of Kalahari within the Rodinia supercontinent. In this study, we present original and compiled zircon U–Pb geochronological and Hf isotopic data spanning ca. 1180 to 950 Ma along with whole-rock Nd isotopes, covering a broad expanse of the Maud Belt and the adjacent Archean Grunehogna Craton, in an attempt to delineate the spatial and temporal patterns of isotopic compositions and evolution, and to better understand the orogenic architecture and style. Spatial isotopic variations are particularly evident in the western front of the orogen (western H.U. Sverdrupfjella) in contrast to other regions. The former exhibits a wide range of isotopic compositions, with the majority showing highly evolved signatures, indicating that the orogenic crust developed through the reworking of pre-existing Archean–Paleoproterozoic continental crust. In contrast, most other regions of the Maud Belt are characterized by relatively juvenile Hf and Nd isotopic compositions, which are interpreted to be derived from a mixture of juvenile magmas and Paleoproterozoic crust. The Hf isotopic evolution from 1180 Ma to 950 Ma indicates significantly less reworking of pre-existing continental crust compared to other contemporaneous Rodinia-forming orogens, including the Grenville Orogen itself, and emphasizes a predominant addition of juvenile material, implying a continuous subduction process. The isotopic investigation in this study, combined with the geological and paleomagnetic evidence, indicates that the Maud Belt most likely represents an exterior accretionary orogen along the eastern margin of the Proto-Kalahari Craton, rather than being part of the continental collision zones that led to Rodinia amalgamation.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; paleogeografi; paleomagnetisme

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Keywords: Sørishavet; geologi; klimaendringer; klimamodeller; oseanografi; paleogeografi; paleoklimatologi; paleoseanografi

Surface processes and drivers of the snow water stable isotopic composition at Dome C, East Antarctica – a multi-dataset and modelling analysis - Ollivier, I.; Steen-Larsen, H. C.; Stenni, B.; Arnaud, L.; Casado, M.; Cauquoin, A.; Dreossi, G.; Genthon, C.; Minster, B.; Picard, G.; Werner, M.; Landais, A. (The Cryosphere, 2025)
Water stable isotope records in polar ice cores have been largely used to reconstruct past local temperatures and other climatic information such as evaporative source region conditions of the precipitation reaching the ice core sites. However, recent studies have identified post-depositional processes taking place at the ice sheet's surface, modifying the original precipitation signal and challenging the traditional interpretation of ice core isotopic records. In this study, we use a combination of existing and new datasets of precipitation, snow surface, and subsurface isotopic compositions (δ18O and deuterium excess (d-excess)); meteorological parameters; ERA5 reanalyses; outputs from the isotope-enabled climate model ECHAM6-wiso; and a simple modelling approach to investigate the transfer function of water stable isotopes from precipitation to the snow surface and subsurface at Dome C in East Antarctica. We first show that water vapour fluxes at the surface of the ice sheet result in a net annual sublimation of snow, from 3.1 to 3.7 mm w.e. yr−1 (water equivalent) between 2018 and 2020, corresponding to 12 % to 15 % of the annual surface mass balance. We find that the precipitation isotopic signal cannot fully explain the mean, nor the variability in the isotopic composition observed in the snow, from annual to intra-monthly timescales. We observe that the mean effect of post-depositional processes over the study period enriches the snow surface in δ18O by 3.0 ‰ to 3.3 ‰ and lowers the snow surface d-excess by 3.4 ‰ to 3.5 ‰ compared to the incoming precipitation isotopic signal. We also show that the mean isotopic composition of the snow subsurface is not statistically different from that of the snow surface, indicating the preservation of the mean isotopic composition of the snow surface in the top centimetres of the snowpack. This study confirms previous findings about the complex interpretation of the water stable isotopic signal in the snow and provides the first quantitative estimation of the impact of post-depositional processes on the snow isotopic composition at Dome C, a crucial step for the accurate interpretation of isotopic records from ice cores.
Keywords: Antarktis; fysisk geografi; geologi; klimamodeller; kryosfæren; paleoklimatologi

Giant pit craters on the modern seafloor above magma-induced hydrothermal vent complexes of Scotia Sea, offshore Antarctica - Somoza, L.; Andreassen, K. M.; Plaza-Faverola, A.; Medialdea, T.; Gafeira, J.; González, F. J.; Dickens, G. R. (Scientific Reports, 2025)
Massive injection of 13C depleted carbon to the ocean and atmosphere coincided with major environmental upheaval multiple times in the geological record. For several events, the source of carbon has been attributed to explosive venting of gas produced when magmatic sills intruded organic-rich sediment. The concept mostly derives from studies of a few ancient sedimentary basins with numerous hydrothermal vent complexes (HTVCs) where craters appear to have formed across large areas of the seafloor at the same time, but good examples remain rare in strata younger than the Early Eocene. We present geophysical data documenting at least 150 large (km-scale) craters on the modern seafloor across ∼148,000 km2 of Scan Basin in the southern Scotia Sea, a remote region offshore Antarctica. Seismic and bathymetric information reveals the craters relate to vertical fluid pipes extending above dome-shaped forced folds and saucer-shaped igneous sills. Presumably, magmatic intrusions deform overlying sediment and produce thermogenic gas, where buoyant hydrothermal fluids migrate upwards from sill flanks through V-shaped gas chimneys to the seafloor. Fluid expulsion, driven by excess pore pressure, enhances vertical conduits and creates collapse structures on the seafloor. Age estimates for sill emplacement and crater formation come from correlations of seismic reflectors with bore hole data collected on IODP Expedition 382. Sills intruded into sediment at least two times, first about 12–13 Ma (Middle Miocene), which occurred with deep intrusions of stacked composite sills, and once about 0.9 Ma and associated with volcanism along Discovery Bank, which may have reactivated previous fluid venting. Crater reactivation has occurred since 0.9 Ma, although probably episodically. Importantly, at present-day, numerous craters related to sills and fluid pipes populate the seafloor above a young sedimentary basin, and the ocean and atmosphere are receiving massive quantities of 13C depleted carbon. The two phenomena are unrelated but, with changes in global climate and sedimentation, the craters could be filled simultaneously and give an impression in the rock record of rapid and coeval formation coincident with carbon emission. Interpretations of ancient HTVCs and their significance to global carbon cycling needs revision with consideration of modern seafloor regions with HTVCs, notably Scan Basin.
Keywords: Scotiahavet; Sørishavet; chronostratigrafi; geologi; klimaendringer; marin geologi; vulkanologi

Features and processes of rock weathering in central Dronning Maud Land, Antarctica - Elvevold, Synnøve; Engvik, Ane K.; Sunde, Øyvind (Geomorphology, 2024)
In this study, we have investigated rock weathering phenomena in the central part of Dronning Maud Land, Antarctica. The area is characterized by low mean annual temperatures (−18 °C), strong katabatic winds, and minimal liquid water at the surface. Weathering features, including ventifacts, tafoni, and grus accumulations, are characterized through field observations, rock surface temperature measurements, and microscopic analysis. Abrasion by sand and ice particles transported by strong winds has locally resulted in ridge-shaped ventifacts and rock surfaces with elongated pits, furrows, and grooves. The abrasion-caused features, such as polished facets, keels, and grooves, indicate a northeast-facing wind direction, aligning with the present-day wind regime. The dominant weathering processes in coarse-grained intrusive rocks are oxidation and granular disintegration. Fe-oxidation induces cracking, increasing the porosity and enhancing susceptibility to further weathering. Additionally, temperature fluctuations on rock surfaces caused by solar radiation create thermal stress, which can lead to the formation of microcracks. These microcracks, formed due to thermal expansion, are likely to propagate through subcritical cracking, which is a slow, long-term process. Together, Fe-oxidation, thermal expansion, and subcritical cracking are important mechanisms contributing to long-term weathering and rock decay. Salt weathering, facilitated by snow and ice meltwater, particularly within tafoni, leads to flaking and disintegration of the parent rock. These findings shed light on the complex interactions shaping the geomorphology of central Dronning Maud Land and provide insights into long-term weathering processes operating in Antarctica's extreme environment.
Keywords: Dronning Maud Land; geologi; geomorfologi

Mineralogical and Geochemical Response to Fluid Infiltration into Cambrian Orthopyroxene-Bearing Granitoids and Gneisses, Dronning Maud Land, Antarctica - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Taubald, Heinrich; Elvevold, Synnøve (Minerals, 2024)
Fluid infiltration into Proterozoic and Early Palaeozoic dry, orthopyroxene-bearing granitoids and gneisses in Dronning Maud Land, Antarctica, has caused changes to rock appearance, mineralogy, and rock chemistry. The main mineralogical changes are the replacement of orthopyroxene by hornblende and biotite, ilmenite by titanite, and various changes in feldspar structure and composition. Geochemically, these processes resulted in general gains of Si, mostly of Al, and marginally of K and Na but losses of Fe, Mg, Ti, Ca, and P. The isotopic oxygen composition (δ18OSMOW = 6.0‰–9.9‰) is in accordance with that of the magmatic precursor, both for the host rock and infiltrating fluid. U-Pb isotopes in zircon of the altered and unaltered syenite to quartz-monzonite indicate a primary crystallization age of 520.2 ± 1.0 Ma, while titanite defines alteration at 485.5 ± 1.4 Ma. Two sets of gneiss samples yield a Rb-Sr age of 517 ± 6 Ma and a Sm-Nd age of 536 ± 23 Ma. The initial Sr and Nd isotopic ratios suggest derivation of the gneisses from a relatively juvenile source but with a very strong metasomatic effect that introduced radiogenic Sr into the system. The granitoid data indicate instead a derivation from Mid-Proterozoic crust, probably with additions of mantle components.
Keywords: Dronning Maud Land; NARE 1996/97; geokjemi; geokronologi; geologi; mineralogi

Permafrost and ground-ice conditions in the Untersee Oasis, Queen Maud Land, East Antarctica - Lacelle, Denis; Verret, Marjolaine; Faucher, Benoit; Fisher, David; Gaudreau, Adam; Pellerin, André; Ecclestone, Miles; Andersen, Dale T. (Antarctic Science, 2024)
Knowledge of Antarctic permafrost is mainly derived from the Antarctic Peninsula and Victoria Land. This study examines the 2019–2023 temperature and humidity conditions, distribution and development of polygonal terrain and the origin of ground ice in soils of the Untersee Oasis. In this region, the surface offset (MAAT ≅ MAGST) and the thermal offset (MAGST ≤ TTIT) reflect the lack of vegetation, absence of persistent snow and a dry soil above the ice table. The mean annual vapour pressure at the ground surface is approximately ~2× higher than in the air but is ~0.67× lower than at the ice table. The size of polygons appears to be in equilibrium with the ice-table depth, and numerical modelling suggests that the depth of the ice table is in turn in equilibrium with the ground surface temperature and humidity. The ground ice at the ice table probably originates from the partial evaporation of snowmelt that infiltrated the dry soil column. As such, the depth of the ice table in this region is set by the water vapour density gradient between the ground surface and the ice-bearing ground, but it is recharged periodically by evaporating snowmelt.
Keywords: Dronning Maud Land; fysisk geografi; geologi; permafrost

Miocene ice sheet dynamics and sediment deposition in the central Ross Sea, Antarctica - McKay, Robert; Cockrell, Jay; Shevenell, Amelia E.; Laberg, Jan Sverre; Burns, Julianne; Patterson, Molly; Kim, Sunghan; Naish, Tim; Harwood, David; Levy, Richard; Marschalek, James; van de Flierdt, Tina; et al. (GSA Bulletin, 2024)
Drill cores from the Antarctic continental shelf are essential for directly constraining changes in past Antarctic Ice Sheet extent. Here, we provide a sedimentary facies analysis of drill cores from International Ocean Discovery Program (IODP) Site U1521 in the Ross Sea, which reveals a unique, detailed snapshot of Antarctic Ice Sheet evolution between ca. 18 Ma and 13 Ma. We identify distinct depositional packages, each of which contains facies successions that are reflective of past baseline shifts in the presence or absence of marine-terminating ice sheets on the outermost Ross Sea continental shelf. The oldest depositional package (>18 Ma) contains massive diamictites stacked through aggradation and deposited in a deep, actively subsiding basin that restricted marine ice sheet expansion on the outer continental shelf. A slowdown in tectonic subsidence after 17.8 Ma led to the deposition of progradational massive diamictites with thin mudstone beds/laminae, as several large marine-based ice sheet advances expanded onto the mid- to outer continental shelf between 17.8 Ma and 17.4 Ma. Between 17.2 Ma and 15.95 Ma, packages of interbedded diamictite and diatom-rich mudstone were deposited during a phase of highly variable Antarctic Ice Sheet extent and volume. This included periods of Antarctic Ice Sheet advance near the outer shelf during the early Miocene Climate Optimum (MCO)—despite this being a well-known period of peak global warmth between ca. 17.0 Ma and 14.6 Ma. Conversely, there were periods of peak warmth within the MCO during which diatom-rich mudstones with little to no ice-rafted debris were deposited, which indicates that the Antarctic Ice Sheet was greatly reduced in extent and had retreated to a smaller terrestrial-terminating ice sheet, most notably between 16.3 Ma and 15.95 Ma. Post-14.2 Ma, diamictites and diatomites contain unambiguous evidence of subglacial shearing in the core and provide the first direct, well-dated evidence of highly erosive marine ice sheets on the outermost continental shelf during the onset of the Middle Miocene Climate Transition (MMCT; 14.2–13.6 Ma). Although global climate forcings and feedbacks influenced Antarctic Ice Sheet advances and retreats during the MCO and MMCT, we propose that this response was nonlinear and heavily influenced by regional feedbacks related to the shoaling of the continental shelf due to reduced subsidence, sediment infilling, and local sea-level changes that directly influenced oceanic influences on melting at the Antarctic Ice Sheet margin. Although intervals of diatom-rich muds and diatomite indicating open-marine interglacial conditions still occurred during (and following) the MMCT, repeated advances of marine-based ice sheets since that time have resulted in widespread erosion and overdeepening in the inner Ross Sea, which has greatly enhanced sensitivity to marine ice sheet instability since 14.2 Ma.
Keywords: Rosshavet; Sørishavet; geologi; oseanografi; paleoklimatologi

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

The Late Holocene deglaciation of James Ross Island, Antarctic Peninsula: OSL and 14C-dated multi-proxy sedimentary record from Monolith Lake - Roman, Matěj; Píšková, Anna; Sanderson, David C.W.; Cresswell, Alan J.; Bulínová, Marie; Pokorný, Matěj; Kavan, Jan; Jennings, Stephen J.A.; Lirio, Juan M.; Nedbalová, Linda; Sacherová, Veronika; Kopalová, Kateřina; et al. (Quaternary Science Reviews, 2024)
Lentic waterbodies provide terrestrial sedimentary archives of palaeoenvironmental change in deglaciated areas of the Antarctic. Knowledge of the long-term evolution of Antarctic palaeoenvironments affords important context to the current marked impacts of climate change in the Polar regions. Here, we present a comprehensively dated, multi-proxy sedimentary record from Monolith Lake, a distal proglacial lake in one of the largest ice-free areas of the Antarctic Peninsula region. Of the two defined sedimentary units in the cores studied, the lower Unit 1 exhibits a homogeneous composition and unvarying proxy data profiles, suggesting rapid clastic deposition under uniform, ice-proximal conditions with a sedimentation rate of ∼1 mm yr−1. 14C and optically stimulated luminescence (OSL) dating bracket the deposition interval to 1.5–2.5 ka BP, with the older age being more probable when compared to independent dating of the local deglaciation. The uppermost 11 cm of the record spans the last ∼2.2 ka BP (maximum age), suggesting a markedly decreased sedimentation rate of ∼0.05 mm yr−1 within Unit 2. Whereas Unit 1 shows only scarce evidence of biological activity, Unit 2 provides an uninterrupted record of diatoms (with 29 species recorded) and faunal subfossils, including the fairy shrimp Branchinecta gaini. Concentrations of organically-derived elements, as well as diatoms and faunal remains, are consistent, implying a gradual increase in lake productivity. These results provide an example of long-term Antarctic ‘greening’ (i.e. increasing organic productivity in terrestrial habitats) from a palaeolimnological perspective. The boundary between Units 1 and 2, therefore, marks the timing of local deglaciation at the final stages of a period of negative glacier mass balance, i.e. the Mid-Late Holocene Hypsithermal. Subsequent Neoglacial cooling is evidenced by the abated influence of glacial meltwater streams and turbidity decline linked to reduced glacier runoff, although most proxy responses mirror the natural proglacial lake ontogeny.
Keywords: Antarktis; diatomeer; geografi; geologi; holocene; innsjøer; paleolimnologi; paleoøkologi

Permafrost Hydrogeology of Taylor Valley, Antarctica: Insights From Deep Electrical Resistivity Tomography - Romano, Valentina; Fischanger, Federico; Wilson, Gary; Sciarra, Alessandra; Mazzini, Adriano; Mazzoli, Claudio; Florindo, Fabio; Tartarello, Maria Chiara; Ascani, Massimiliano; Anderson, Jacob; Worthington, Rachel; Hardie, Richard; et al. (Geophysical Research Letters, 2024)
Abstract Global warming has prompted globally widespread permafrost thawing, resulting in enhanced greenhouse gas release into the atmosphere. Studies conducted in the Northern Hemisphere reveal an alarming increase in permafrost thawing. However, similar data from Antarctica are scarce. We conducted a 2-D Deep Electrical Resistivity Tomography (DERT) survey in Taylor Valley, Antarctica, to image the distribution of permafrost, its thicknesses, lower boundaries, and hydrogeology. Results show resistive, discontinuous domains that we suggest represent permafrost units. We also find highly conductive layers (5?10 Ω·m), between 300?350 m and 600?650 m below ground level and a shallower (?50?100 m depth) conductive layer. The combined data set reveals a broad brine system in Taylor Valley, implying multi-tiered groundwater circulation: a shallow, localized system linked with surface water bodies and a separate deeper, regional circulation system. The arrangement of these brines across different levels, coupled with the uneven permafrost distribution, underscores potential interplay between the two systems.
Keywords: Antarktis; geologi; global oppvarming; hydrogeologi; klimaendringer; permafrost

Eccentricity pacing and rapid termination of the early Antarctic ice ages - van Peer, Tim E.; Liebrand, Diederik; Taylor, Victoria E.; Brzelinski, Swaantje; Wolf, Iris; Bornemann, André; Friedrich, Oliver; Bohaty, Steven M.; Xuan, Chuang; Lippert, Peter C.; Wilson, Paul A. (Nature Communications, 2024)
Earth’s obliquity and eccentricity cycles are strongly imprinted on Earth’s climate and widely used to measure geological time. However, the record of these imprints on the oxygen isotope record in deep-sea benthic foraminifera (δ18Ob) shows contradictory signals that violate isotopic principles and cause controversy over climate-ice sheet interactions. Here, we present a δ18Ob record of high fidelity from International Ocean Drilling Program (IODP) Site U1406 in the northwest Atlantic Ocean. We compare our record to other records for the time interval between 28 and 20 million years ago, when Earth was warmer than today, and only Antarctic ice sheets existed. The imprint of eccentricity on δ18Ob is remarkably consistent globally whereas the obliquity signal is inconsistent between sites, indicating that eccentricity was the primary pacemaker of land ice volume. The larger eccentricity-paced early Antarctic ice ages were vulnerable to rapid termination. These findings imply that the self-stabilizing hysteresis effects of large land-based early Antarctic ice sheets were strong enough to maintain ice growth despite consecutive insolation-induced polar warming episodes. However, rapid ice age terminations indicate that resistance to melting was weaker than simulated by numerical models and regularly overpowered, sometimes abruptly.
Keywords: Antarktis; geologi; paleoklimatologi; paleoseanografi

Highly stratified mid-Pliocene Southern Ocean in PlioMIP2 - Weiffenbach, J. E.; Dijkstra, H. A.; von der Heydt, A. S.; Abe-Ouchi, A.; Chan, W.-L.; Chandan, D.; Feng, R.; Haywood, A. M.; Hunter, S. J.; Li, X.; Otto-Bliesner, B. L.; Peltier, W. R.; et al. (Clim. Past, 2024)
During the mid-Pliocene warm period (mPWP; 3.264–3.025 Ma), atmospheric CO2 concentrations were approximately 400 ppm, and the Antarctic Ice Sheet was substantially reduced compared to today. Antarctica is surrounded by the Southern Ocean, which plays a crucial role in the global oceanic circulation and climate regulation. Using results from the Pliocene Model Intercomparison Project (PlioMIP2), we investigate Southern Ocean conditions during the mPWP with respect to the pre-industrial period. We find that the mean sea surface temperature (SST) warming in the Southern Ocean is 2.8 °C, while global mean SST warming is 2.4 °C. The enhanced warming is strongly tied to a dramatic decrease in sea ice cover over the mPWP Southern Ocean. We also see a freshening of the ocean (sub)surface, driven by an increase in precipitation over the Southern Ocean and Antarctica. The warmer and fresher surface leads to a highly stratified Southern Ocean that can be related to weakening of the deep abyssal overturning circulation. Sensitivity simulations show that the decrease in sea ice cover and enhanced warming is largely a consequence of the reduction in the Antarctic Ice Sheet. In addition, the mPWP geographic boundary conditions are responsible for approximately half of the increase in mPWP SST warming, sea ice loss, precipitation, and stratification increase over the Southern Ocean. From these results, we conclude that a strongly reduced Antarctic Ice Sheet during the mPWP has a substantial influence on the state of the Southern Ocean and exacerbates the changes that are induced by a higher CO2 concentration alone. This is relevant for the long-term future of the Southern Ocean, as we expect melting of the western Antarctic Ice Sheet in the future, an effect that is not currently taken into account in future projections by Coupled Model Intercomparison Project (CMIP) ensembles.
Keywords: Sørishavet; geologi; klimamodeller; klimatologi; oseanografi; paleoklimatologi

A continent-wide detailed geological map dataset of Antarctica - Cox, Simon C.; Smith Lyttle, Belinda; Elkind, Samuel; Smith Siddoway, Christine; Morin, Paul; Capponi, Giovanni; Abu-Alam, Tamer; Ballinger, Matilda; Bamber, Lauren; Kitchener, Brett; Lelli, Luigi; Mawson, Jasmine; et al. (Scientific Data, 2023)
A dataset to describe exposed bedrock and surficial geology of Antarctica has been constructed by the GeoMAP Action Group of the Scientific Committee on Antarctic Research (SCAR) and GNS Science. Our group captured existing geological map data into a geographic information system (GIS), refined its spatial reliability, harmonised classification, and improved representation of glacial sequences and geomorphology, thereby creating a comprehensive and coherent representation of Antarctic geology. A total of 99,080 polygons were unified for depicting geology at 1:250,000 scale, but locally there are some areas with higher spatial resolution. Geological unit definition is based on a mixed chronostratigraphic- and lithostratigraphic-based classification. Description of rock and moraine polygons employs the international Geoscience Markup Language (GeoSciML) data protocols to provide attribute-rich and queryable information, including bibliographic links to 589 source maps and scientific literature. GeoMAP is the first detailed geological map dataset covering all of Antarctica. It depicts ‘known geology’ of rock exposures rather than ‘interpreted’ sub-ice features and is suitable for continent-wide perspectives and cross-discipline interrogation.
Keywords: Antarktis; geologi; geomorfologi

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - Ruggiero, L.; Sciarra, A.; Mazzini, A.; Florindo, F.; Wilson, G.; Tartarello, M.C.; Mazzoli, C.; Anderson, J.T.H.; Romano, V.; Worthington, R.; Bigi, S.; Sassi, R.; et al. (Science of The Total Environment, 2023)
Ongoing studies conducted in northern polar regions reveal that permafrost stability plays a key role in the modern carbon cycle as it potentially stores considerable quantities of greenhouse gases. Rapid and recent warming of the Arctic permafrost is resulting in significant greenhouse gas emissions, both from physical and microbial processes. The potential impact of greenhouse gas release from the Antarctic region has not, to date, been investigated. In Antarctica, the McMurdo Dry Valleys comprise 10 % of the ice-free soil surface areas in Antarctica and like the northern polar regions are also warming albeit at a slower rate. The work presented herein examines a comprehensive sample suite of soil gas (e.g., CO2, CH4 and He) concentrations and CO2 flux measurements conducted in Taylor Valley during austral summer 2019/2020. Analytical results reveal the presence of significant concentrations of CO2, CH4 and He (up to 3.44 vol%, 18,447 ppmv and 6.49 ppmv, respectively) at the base of the active layer. When compared with the few previously obtained measurements, we observe increased CO2 flux rates (estimated CO2 emissions in the study area of 21.6 km2 ≈ 15 tons day−1). We suggest that the gas source is connected with the deep brines migrating from inland (potentially from beneath the Antarctic Ice Sheet) towards the coast beneath the permafrost layer. These data provide a baseline for future investigations aimed at monitoring the changing rate of greenhouse gas emissions from Antarctic permafrost, and the potential origin of gases, as the southern polar region warms.
Keywords: Antarktis; drivhusgasser; geofysikk; geologi; geostatistikk; isbreer; permafrost

Southern Ocean biogenic blooms freezing-in Oligocene colder climates - Hochmuth, Katharina; Whittaker, Joanne M.; Sauermilch, Isabel; Klocker, Andreas; Gohl, Karsten; LaCasce, Joseph H. (Nature Communications, 2022)
Crossing a key atmospheric CO2 threshold triggered a fundamental global climate reorganisation ~34 million years ago (Ma) establishing permanent Antarctic ice sheets. Curiously, a more dramatic CO2 decline (~800–400 ppm by the Early Oligocene(~27 Ma)), postdates initial ice sheet expansion but the mechanisms driving this later, rapid drop in atmospheric carbon during the early Oligocene remains elusive and controversial. Here we use marine seismic reflection and borehole data to reveal an unprecedented accumulation of early Oligocene strata (up to 2.2 km thick over 1500 × 500 km) with a major biogenic component in the Australian Southern Ocean. High-resolution ocean simulations demonstrate that a tectonically-driven, one-off reorganisation of ocean currents, caused a unique period where current instability coincided with high nutrient input from the Antarctic continent. This unrepeated and short-lived environment favoured extreme bioproductivity and enhanced sediment burial. The size and rapid accumulation of this sediment package potentially holds ~1.067 × 1015 kg of the ‘missing carbon’ sequestered during the decline from an Eocene high CO2-world to a mid-Oligocene medium CO2-world, highlighting the exceptional role of the Southern Ocean in modulating long-term climate.
Keywords: Sørishavet; geologi; glasiologi; klimaendringer; sedimenter

På jobb - lang borte fra kontoret - blant spektakulære fjell og landskap - Elvevold, Synnøve (Polarboken, 2022)
Keywords: Dronning Maud Land; geologi

Cavernous Decay of Granite and Granitic Gneiss, Central Dronning Maud Land, Antarctica - Engvik, Ane K; Elvevold, Synnøve; Myhre, Per Inge (The Journal of Geology, 2022)
Tafoni are a type of cavernous weathering that is found in a variety of rock types and locations around the world. Tafoni have been documented in a number of climatic zones ranging from hot and cold deserts to moist coastal environments. Despite the widespread distribution of tafoni, the major processes controlling tafoni weathering are not well understood and are still a matter of discussion. This study addresses the frequent distribution of well-developed tafoni in the cold, arid environment of the inland mountain range of central Dronning Maud Land, Antarctica. The aim is to document and characterize the nature of tafoni present in Gjelsvikfjella (2°E) eastward to Filchnerfjella (8°E) and to discuss formation processes. The cavities occur in groups and are typically spherical to oval shaped. They range in diameter and depth from 1 dm up to 1.5 m. The cold, arid environment of this region favors mechanical weathering mechanisms such as freeze-thaw actions and wind abrasion. Furthermore, the structural, textural, and mineralogical properties of the parent rock can potentially have a strong control on weathering and cavity development. Observed tafoni are typically formed in massive granitoid intrusives and granitic gneisses and migmatites. Chemical dissolution of pyroxene to iddingsite and radiation from rare earth element–bearing accessory minerals cause microfracturing, which facilitates freeze-thaw actions and accordingly enhances the weathering.
Keywords: Dronning Maud Land; geologi

Geologisk feltarbeid i Antarktis - Sunde, Øyvind; Elvevold, Synnøve; Engvik, Ane K.; Tholfsen, Audun (Geonytt : et medlemsblad for Norsk geologisk forening, 2022)
Dronning Maud Land, som er Norges territoriale krav i Antarktis, utgjør nærmere 1/6 av det antarktiske kontinentet. Geologisk kartlegging og forskning i Dronning Maud Land er en nasjonal oppgave og i Antarktis-sammenheng kan det betraktes som en måte å vise fortsatt interesse i Norges territoriale krav.
Keywords: Dronning Maud Land; geologi

Banded Charnockite: The Result of Crustal Magma Generation, Piecemeal Emplacement, and Fluid-Driven Mineral Replacement in High-Grade Crust (Central Dronning Maud Land, Antarctica) - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Elvevold, Synnøve (The Journal of Geology, 2021)
AbstractOur study of a banded charnockite complex of the Mühlig-Hofmannfjella in Dronning Maud Land, Antarctica, illustrates how the combination of high-temperature (re-)crystallization processes, melts, and volatile fluids leads to complex intrusive, metasomatic, and structural relationships. The igneous complex consists of gently dipping sets of charnockite interlayered with dolerite and leucogranite. The banded complex formed primarily by magmatic processes, but with superimposed modifications by metasomatism. The charnockite has a ferroan composition and contains both orthopyroxene (Fs80?84) and olivine (Fa94?96). Zircon U-Pb dates the emplacement of charnockite at 515 Ma, and inherited zircon cores and negative εNd values of ?3 to ?5 indicate that the age of the source of the magma was about 1100 Ma. Neodymium isotopes were not homogenized during the Cambrian magmatic event, which suggests that the generation and emplacement of the magma took place in separate batches during construction of the banded complex. By contrast, the Rb-Sr system in the charnockite was extensively homogenized, likely because of the superimposed late-magmatic fluid activity, which also produced the bands and networks of leucogranites. These events occurred during the late stages of the assembly of Gondwana, with postcollisional extension and mantle upwelling maintaining a high heat flow.
Keywords: Dronning Maud Land; geologi

Moving mountains - when rocks and fluids interact - Engvik, Ane K.; Elvevold, Synnøve; Myhre, Per Inge; Sunde, Øyvind; Austrheim, Håkon (Fram forum, 2021)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Substantial spatial variation in glacial erosion rates in the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna K (Communications Earth & Environment, 2021)
The coast-parallel Dronning Maud Land (DML) mountains represent a key nucleation site for the protracted glaciation of Antarctica. Their evolution is therefore of special interest for understanding the formation and development of the Antarctic ice sheet. Extensive glacial erosion has clearly altered the landscape over the past 34 Myr. Yet, the total erosion still remains to be properly constrained. Here, we investigate the power of low-temperature thermochronology in quantifying glacial erosion in-situ. Our data document the differential erosion along the DML escarpment, with up to c. 1.5 and 2.4 km of erosion in western and central DML, respectively. Substantial erosion at the escarpment foothills, and limited erosion at high elevations and close to drainage divides, is consistent with an escarpment retreat model. Such differential erosion suggests major alterations of the landscape during 34 Myr of glaciation and should be implemented in future ice sheet models.
Keywords: Dronning Maud Land; geologi; geomorfologi

Prolonged high-grade metamorphism of supracrustal gneisses from Mühlig-Hofmannfjella, central Dronning Maud Land (East Antarctica) - Elvevold, Synnøve; Engvik, Ane K.; Abu-Alam, Tamer S.; Myhre, Per Inge; Corfu, Fernando (Precambrian Research, 2020)
The bedrock of Mühlig-Hofmannfjella, central Dronning Maud Land in eastern Antarctica, is part of the high-grade Maud Belt and comprises a deep-seated metamorphic-plutonic complex. The P-T-t evolution of anatectic supracrustal gneisses has been recovered through a study of mineral assemblages, textural relationships and U-Pb ID TIMS geochronology on zircon and monazite followed by pseudosection modelling. Peak conditions reached granulite facies conditions (T ≥ 810–820 °C) at moderate crustal depths (P = ca. 8 kbar) and resulted in partial melting. Peak-pressure conditions were followed by isothermal decompression at elevated temperatures. After exhumation to crustal levels of about 4–5 kbar, the area underwent a final near-isobaric cooling, which is documented by a secondary growth of garnet. Zircons indicate a period of growth at 570–566 Ma, whereas monazite ages range from 610 to 525 Ma. A likely heat source for the granulite facies metamorphism is decay of radioactive heat-producing elements in the core of the orogen. The combined geochronology and metamorphic data indicate a prolonged, clockwise P-T path, which reflects collision and formation of a long-lived orogenic plateau.
Keywords: Antarktis; Dronning Maud Land; geologi

Neoproterozoic geodynamic evolution of easternmost Kalahari: Constraints from U-Pb-Hf-O zircon, Sm-Nd isotope and geochemical data from the Schirmacher Oasis, East Antarctica - Jacobs, Joachim; Mikhalsky, Evgeny; Henjes-Kunst, Friedhelm; Läufer, Andreas; Thomas, Robert J; Elburg, Marlina; Wang, Chengcheng; Estrada, Solveig; Skublov, S G (Precambrian Research, 2020)
Late Tonian (ca. 785–760 Ma) granodioritic to granitic orthogneisses of the Schirmacher Oasis region in Dronning Maud Land (DML), East Antarctica, are interpreted as recording an active continental margin setting at the periphery of Kalahari and Rodinia. The rocks probably represent exposures of a significant tectonic province hidden beneath the ice, the erosional remnants of which are recorded as detrital zircons in late Tonian-Cryogenian metasedimentary rocks throughout central and eastern DML, as well as in ice-rafted debris from recent sediments offshore Dronning Maud Land. The orthogneisses have single-stage Sm-Nd model ages of ca. 1.3–1.5 Ga and zircon Hf-signatures (εHft = +2 – +5), indistinguishable from the adjacent Grenville-age basement rocks of easternmost Kalahari. Their geochemistry suggests that they evolved in the late stages of a continental margin magmatic arc and possibly within a roll-back tectonic framework, suggestive of subduction of relatively old oceanic lithosphere. The eastern Kalahari continental arc is one of a number of continental arcs that characterize the western part of the fragmenting Rodinia and document the supercontinent “turning inside out” after its formation at ca. 1000 Ma and a period of relative tectonic quiescence between ca. 900 and 800 Ma. The rocks show an ultra-high temperature metamorphic overprint that was accompanied by syn-tectonic magmatism from ca. 650 to 600 Ma. The high temperature metamorphism is interpreted to relate to back-arc extension that also led to major anorthosite magmatism elsewhere, prior to continental collision in the region. The rocks lack the subsequent widespread high-grade metamorphic overprint at ca. 590–500 Ma which occurs in the adjacent regions due to Himalayan-style continental collision along the East African-Antarctic Orogen during Gondwana assembly.
Keywords: Dronning Maud Land; geokronologi; geologi

New Antarctic clawed lobster species (Crustacea: Decapoda: Nephropidae) from the Upper Cretaceous of James Ross Island - Pinheiro, Allysson P; Saraiva, Antônio Álamo Feitosa; Santana, William; Sayão, Juliana Manso; Figueiredo, Rodrigo Giesta; Rodrigues, Taissa; Weinschütz, Luiz Carlos; Ponciano, Luiza Corral Martins de Oliveira; Kellner, Alexander Wilhelm Armin (Polar Research, 2020)
A new species of nephropid lobster, Hoploparia echinata sp. nov., from the James Ross Island in the Antarctic Peninsula is here described and illustrated. The material was collected in the Santa Marta Formation (Santonian–-Campanian), the basal unit of the Marambio Group, Larsen Basin, located in the western portion of the Antarctic Peninsula. Hoploparia echinata sp. nov. can easily be differentiated from its congeners by the presence of distinct short spines on dorsal and ventral margins on the third maxillipeds, merus of the chelipeds and pereopods; these are the characters not described in other Hoploparia species so far.
Keywords: Antarktis; fossiler; geologi; langhalekreps; paleobiologi; paleogeografi; paleontologi; zoologi

Microcontinents and Continental Fragments Associated With Subduction Systems - van den Broek, Joost M; Gaina, Carmen (Tectonics, 2020)
Microcontinents and continental fragments are small pieces of continental crust that are surrounded by oceanic lithosphere. Although classically associated with passive margin formation, here we present several preserved microcontinents and continental fragments associated with subduction systems. They are located in the Coral Sea, South China Sea, central Mediterranean and Scotia Sea regions, and a “proto-microcontinent,” in the Gulf of California. Reviewing the tectonic history of each region and interpreting a variety of geophysical data allows us to identify parameters controlling the formation of microcontinents and continental fragments in subduction settings. All these tectonic blocks experienced long, complex tectonic histories with an important role for developing inherited structures. They tend to form in back-arc locations and separate from their parent continent by oblique or rotational kinematics. The separated continental pieces and associated marginal basins are generally small and their formation is quick (<50 Myr). Microcontinents and continental fragments formed close to large continental masses tend to form faster than those created in systems bordered by large oceanic plates. A common triggering mechanism for their formation is difficult to identify, but seems to be linked with rapid changes of complex subduction dynamics. The young ages of all contemporary pieces found in situ suggest that microcontinents and continental fragments in these settings are short lived. Although presently the amount of in-situ subduction-related microcontinents is meager (an area of 0.56% and 0.28% of global, non-cratonic, continental crustal area and crustal volume, respectively), through time microcontinents contributed to terrane amalgamation and larger continent formation.
Keywords: Sørishavet; batymetri; geofysikk; geologi; geovitenskap; litosfæren; tektonikk

Late Neoproterozoic–Cambrian magmatism in Dronning Maud Land (East Antarctica): U–Pb zircon geochronology, isotope geochemistry and implications for Gondwana assembly - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Elvevold, Synnøve (Precambrian Research, 2020)
Dronning Maud Land (DML) is a key area for the better understanding of the geotectonic history and amalgamation processes of the southern part of Gondwana. Here, we present comprehensive new zircon U–Pb–Hf–O, whole-rock Sm–Nd isotopic and geochemical data for late Neoproterozoic-Cambrian igneous rocks along a profile from central to eastern DML, which provides new insights into the crustal evolution and tectonics of the region. In central DML, magmatism dominantly occurred at 530–485 Ma, with 650–600 Ma charnockite and anorthosite locally distributed at its eastern periphery. In contrast, eastern DML experienced long-term and continuous granitic magmatism from ca. 650 Ma to 500 Ma. In central DML, the 650–600 Ma samples are characterized by highly elevated δ18O (7.5–9.5‰) associated with slightly negative to positive εHf(t) values (−1 to +3), indicating significant addition of high-δ18O crustal components, such as sedimentary material at the margin of the Kalahari Craton. Evolved Hf isotopic signatures (εHf(t) = −15 to −6) and moderately elevated O isotopic data (δ18O = 6–8‰) of the Cambrian granitic rocks from central DML indicate a significant incorporation of the pre-existing, old continental crust. In eastern DML, the suprachondritic Hf–Nd isotope signatures and moderate δ18O values of the late Neoproterozoic granites (650–550 Ma) from the Sør Rondane Mountains support the view that they mainly originated from crust of the Tonian Oceanic Arc Super Terrane (TOAST). The post-540 Ma granites, however, have more evolved Hf and Nd isotopic compositions, suggesting an increasing involvement of older continental components during Cambrian magmatism. Nd isotopes of the Cambrian granitic rocks in DML display an increasingly more radiogenic composition towards the east with model ages ranging from late Archean to Mesoproterozoic times, which is in line with the isotopic trend of the Precambrian basement in this region. The late Neoproterozoic (>600 Ma) igneous rocks in central and eastern DML were emplaced in two independent subduction systems, at the periphery of the eastern Kalahari Craton and somewhere within the Mozambique Ocean respectively. The accretion and assembly of the TOAST to the eastern margin of the Kalahari Craton and their collision with surrounding continental blocks was followed by extensive post-collisional magmatism due to delamination tectonics and orogenic collapse in the Cambrian. The late Neoproterozoic–Cambrian igneous rocks in DML thus record an orogenic cycle from subduction-accretion, continental collision to post-collisional process during and after the assembly of Gondwana.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi

Grenville-age continental arc magmatism and crustal evolution in central Dronning Maud Land (East Antarctica): Zircon geochronological and Hf–O isotopic evidence - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Thomas, Robert J.; Elvevold, Synnøve (Gondwana Research, 2020)
This study focusses on the Grenville-age Maud Belt in Dronning Maud Land (DML), East Antarctica, which was located at the margin of the Proto-Kalahari Craton during the assembly of Rodinia. We present new U–Pb zircon ages and Hf–O isotope analyses of mafic and granitic gneisses exposed in the Orvin-Wohlthat Mountains and Gjelsvikfjella, central DML (cDML). The geochronological data indicate continuous magmatic activity from 1160 to 1070 Ma which culminated at 1110–1090 Ma, followed by high-grade metamorphism between 1080 and 1030 Ma. The majority of zircons from the Orvin-Wohlthat Mountains exhibit radiogenic Hf isotopic compositions corresponding to suprachondritic εHf (t) values and Mesoproterozoic model ages, indicating crystallization from predominantly juvenile magmas. However, the involvement of ancient sedimentary material, which were most likely derived from the adjacent Proto-Kalahari Craton, is revealed by a few samples with negative to neutral εHf (t) and significantly elevated δ18O values (8–10‰). Samples from further west, in Gjelsvikfjella have more mantle-like zircon O isotopic compositions and late Paleoproterozoic Hf model ages, indicating the incorporation of ancient, previously mantle-derived continental crust. The rocks in cDML, thus define part of an extensive Mesoproterozoic magmatic arc with subduction under the Proto-Kalahari margin. This involved significant growth of new continental crust, possibly related to slab retreat, accompanied by subordinate recycling of older crustal components. The Maud Belt has previously been correlated with the 1250–1030 Ma Natal Belt in southern Africa, which lay to the west in the context of Gondwana, although this assertion has recently been questioned. Our study supports the latter view in demonstrating that the continental arc magmatism in the Maud Belt appears to be temporally and tectonically unconnected to the accretion of (slightly older) juvenile oceanic islands in the Natal Belt, which, in contrast to the Maud Belt, show subduction polarity away from the craton. We thus speculate that the Namaqua-Natal to Maud Belt contact (exposed in the Heimefront Shear Zone) may represent a changed tectonic environment from arc/continent-continent collision to slightly younger continental margin orogenesis at the westernmost termination of this part of the global Grenville Orogen. The Maud Belt marks the beginning of a major, long-lived accretionary Andean-type tectonic regime on the eastern margin of Proto-Kalahari in the Meso-Neoproterozoic during Rodinia assembly and break-up until the formation of Gondwana.
Keywords: Dronning Maud Land; geologi

Geological mapping of Norway's least explored mountains - Elvevold, Synnøve; Myhre, Per Inge; Engvik, Ane K; Jacobs, Joachim (Fram forum, 2019)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging; nunataker

Vannet som forandret fjellene - Engvik, Ane K (Bergtatt - Ane K. Engviks blogg, 2019)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Groundwater discharge to the western Antarctic coastal ocean - Null, Kimberly A; Corbett, D Reide; Crenshaw, Jared; Peterson, Richard N; Peterson, Leigha E; Lyons, W Berry (Polar Research, 2019)
Submarine groundwater discharge (SGD) measurements have been limited along the Antarctic coast, although groundwater discharge is becoming recognized as an important process in the Antarctic. Quantifying this meltwater pathway is important for hydrologic budgets, ice mass balances and solute delivery to the coastal ocean. Here, we estimate the combined discharge of subglacial and submarine groundwater to the Antarctic coastal ocean. SGD, including subglacial and submarine groundwater, is quantified along the WAP at the Marr Glacier terminus using the activities of naturally occurring radium isotopes (223Ra, 224Ra). Estimated SGD fluxes from a 224Ra mass balance ranged from (0.41 ± 0.14)×104 and (8.2 ± 2.3)×104m3 d−1. Using a salinity mass balance, we estimate SGD contributes up to 32% of the total freshwater to the coastal environment near Palmer Station. This study suggests that a large portion of the melting glacier may be infiltrating into the bedrock and being discharged to coastal waters along the WAP. Meltwater infiltrating as groundwater at glacier termini is an important solute delivery mechanism to the nearshore environment that can influence biological productivity. More importantly, quantifying this meltwater pathway may be worthy of attention when predicting future impacts of climate change on retreat of tidewater glaciers.
Keywords: Sørishavet; biologi; geologi; grunnvann; hydrologi; isbreer; klimaendringer; tidevann

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

Provenance, transport and diagenesis of sediment in polar areas: a case study in Profound Lake, King George Island, Antarctica - Hernández, Ana C; Bastias, Joaquin; Matus, Daniela; Mahaney, William C (Polar Research, 2018)
Detailed scanning electron microscopy (SEM) micro-texture and mineralogical analysis of lacustrine sediment recovered from Profound Lake (also known as Uruguay Lake), Antarctica, was conducted in the foreland area of the Collins Glacier, King George Island. Very coarse and coarse sand grade size fractions (2 mm – 600 μm) were examined with SEM/ energy dispersive spectrometry, while the total sand fraction and fines (silt + clay) were examined using x-ray diffraction to determine relationships to source rock, weathering and transport history and long-term clay mineral weathering, all of which are poorly understood in polar areas. The mineralogy of these sediments was compared with petrographical information of the country rock to identify potential detrital sources. The association of recovered detrital minerals, sometimes strongly pre-weathered, supports release from source rock of basaltic and andesitic compositions. The micro-texture analysis of quartz, magnetite and various plagioclase grains show micro-features that reveal a complex weathering–diagenesis history tentatively extending into the Paleogene. The bedrock was eroded mostly by glacial processes and mechanical action presumed to result from glacial crushing. Alteration minerals, likely the product of pre-weathering, are probably sourced from weathered bedrock during contact with the sub-aerial atmosphere prior to entrainment. However, amorphous silica precipitation indicates weathering subsequent to glacial erosion from the source bedrock. Cracks of variable dimensions are mostly characteristic of either frost weathering or glacial transport, and involve mechanical and chemical processes.
Keywords: Antarktis; geologi; mineralogi; petrografi; polarområdene; sedimentologi

Transpression and tectonic exhumation in the Heimefrontfjella, western orogenic front of the East African/Antarctic Orogen, revealed by quartz textures of high strain domains - Bauer, Wilfried; Siemes, Heinrich; Spaeth, Gerhard; Jacobs, Joachim (Polar Research, 2016)
The metamorphic basement of the Heimefrontfjella in western Dronning Maud Land (Antarctica) forms the western margin of the major ca. 500 million year old East African/East Antarctic Orogen that resulted from the collision of East Antarctica and greater India with the African cratons. The boundary between the tectonothermally overprinted part of the orogen and its north-western foreland is marked by the subvertical Heimefront Shear Zone. North-west of the Heimefront Shear Zone, numerous low-angle dipping ductile thrust zones cut through the Mesoproterozoic basement. Petrographic studies, optical quartz c-axis analyses and x-ray texture goniometry of quartz-rich mylonites were used to reveal the conditions that prevailed during the deformation. Mineral assemblages in thrust mylonites show that they were formed under greenschist-facies conditions. Quartz microstructures are characteristic of the subgrain rotation regime and oblique quartz lattice preferred orientations are typical of simple shear-dominated deformation. In contrast, in the Heimefront Shear Zone, quartz textures indicate mainly flattening strain with a minor dextral rotational component. These quartz microstructures and lattice preferred orientations show signs of post-tectonic annealing following the tectonic exhumation. The spatial relation between the sub-vertical Heimefront Shear Zone and the low-angle thrusts can be explained as being the result of strain partitioning during transpressive deformation. The pure-shear component with a weak dextral strike-slip was accommodated by the Heimefront Shear Zone, whereas the north–north-west directed thrusts accommodate the simple shear component with a tectonic transport towards the foreland of the orogen. Keywords: Dronning Maud Land; quartz microfabrics; X-ray texture goniometry; shear zones; mylonites.
Keywords: Dronning Maud Land; geologi; mylonitter; petrografi; tektonikk

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica - Peacock, Jared; Selway, Kate (Journal of Geophysical Research: Solid Earth, 2016)
The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glacier and regions inland of the Vestfold Hills and Rauer Group islands. Time-frequency analysis of the MT time series yielded three important observations: (1) Wind speeds in excess of ∼8 m/s reduce coherence between electric and magnetic fields due to charged wind-blown particles of ice and snow. (2) Estimation of the MT transfer function is best between 1000 and 1400 UT when ionospheric Hall currents enhance the magnetic source field. (3) Nonplanar source field effects were minimal but detectable and removed from estimation of the MT transfer function. Inversions of MT data in 2-D and 3-D produce similar resistivity models, where structures in the preferred 3-D resistivity model correlate strongly with regional magnetic data. The electrically conductive Rauer Group is separated from the less conductive Vestfold Hills by a resistive zone under the Sørsdal Glacier, which is interpreted to be caused by oxidation during suturing. Though a suture zone has been imaged, no time constrains on suturing can be made from the MT data.
Keywords: Antarktis; geofysikk; geologi; magnetotelluriske målinger

Investigating uncertainty in the simulation of the Antarctic ice sheet during the mid-Piacenzian - Yan, Qing; Zhang, Zhongshi; Wang, Huijun (Journal of Geophysical Research: Atmospheres, 2016)
The mid-Piacenzian (~3 Ma) represents the most recent warm period in Earth's history on a geological time scale; it is characterized by a significant rise of global sea level. The simulation of the size and location of the ice sheets and the investigation of the uncertainty in the simulations are potentially helpful for constraining reconstructed sea level changes. In this study, we focus on the behavior of the Antarctic ice sheet (AIS) in the mid-Piacenzian. We investigate the influence of topography correction, model parameters, climate forcings, and model resolution on the modeled AIS and explore the isolated role of atmospheric and oceanic forcings. Forced by the simulated climate changes with the Norwegian Earth System Model, the Parallel Ice Sheet Model (15 km × 15 km) produces a nearly collapsed West AIS (WAIS) in the mid-Piacenzian, with no significant retreat of the East AIS (EAIS). The role of increased air temperature plays a key role in the mass loss of the mid-Piacenzian AIS, while its role is comparable to the role of ocean warming on the melting of the WAIS. In terms of the range of sea level changes, the largest source of uncertainty in the modeled AIS is derived from ice sheet model parameters and climate forcings. Although the employed model parameters, topography correction factors, and model resolution affect the simulated AIS in the mid-Piacenzian, large-scale deglaciation of the EAIS in our sensitivity experiments may only be possible with additional warming.
Keywords: Antarktis; atmosfæren; geologi; havnivåstigning; innlandsis; klimaendringer; paleontologi

Two distinct Late Mesoproterozoic/Early Neoproterozoic basement provinces in central/eastern Dronning Maud Land, East Antarctica: The missing link, 15–21°E - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Kleinhanns, Ilka C; Henjes-Kunst, Friedhelm; Estrada, Solveig; Ruppel, Antonia S; Damaske, Detlef; Montero, Pilar; Bea, Fernando (Precambrian Research, 2015)
This article highlights the field geology, geochronology and geochemistry of an important and previously unstudied region between eastern (Sør Rondane Mountains) and central Dronning Maud Land (DML). The area allows the characterisation and ground-truthing of a large and mostly ice-covered area that is geophysically distinct and which was previously interpreted as a potentially older cratonic block south of a Late Neoproterozoic/Early Paleozoic (LN/EP) mobile belt, as exposed in the Sør Rondane Mts. (SRM). SHRIMP/SIMS zircon analyses of 20 samples together with new geochemistry indicate that the exposed basement consists of a ca. 1000–900Ma juvenile terrane that is very similar to the juvenile rocks of the SW-Terrane of the SRM, a characteristic gabbro–trondhjemite–tonalite–granite (GTTG) suite, with normalised trace element patterns typical for subduction-related magmas and mostly positive initial epsilon Nd values. The area shows strong LN/EP crustal reworking, migmatisation and melt production, including 560–530Ma A-type magmatism. Therefore, this area is very similar to the SW-Terrane and differs only in the degree of LN/EP reworking. We interpret the SW-Terrane of Sør Rondane as a mega-boudin sandwiched in between rheologically weaker portions of similar oceanic arc terranes. Therefore, the study area, and thereby the aeromagnetically distinct SE DML province does neither represent the foreland of a LN/EP mobile belt, nor a craton, as speculated based on geophysical data alone. Instead, a large Tonian Oceanic Arc Super Terrane (TOAST) with significant extent emerges. Its western limit is represented by the Forster Magnetic Anomaly, which represents a suture to the Grenville-age Maud Belt. East of the TOAST, the Rayner Complex is similar in age but otherwise distinctly different. The Rayner Complex has a much longer history of island arc accretions with continent–continent collision at ca. 950Ma and it has markedly more evolved crust. In contrast, the TOAST has a pronounced juvenile character without significant inheritance and lacks metamorphic overprint immediately following crust formation. This indicates that it has not been an integral part of Rodinia. The eastern boundary of the TOAST is probably in the vicinity of the Yamato Mts., whilst its northern extension might be seen in the Vohibori Terrane (SW Madagascar), which in turn could correlate with the Arabian Nubian Shield. The LN/EP tectono-metamorphic overprint of the TOAST shows a slight decrease in ages from W to E, possibly indicating that it first amalgamated on its Kalahari side before it was attached to Rukerland/Indo-Antarctica.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi

The Main Shear Zone in Sør Rondane, East Antarctica: Implications for the late-Pan-African tectonic evolution of Dronning Maud Land - Ruppel, Antonia S; Läufer, Andreas; Jacobs, Joachim; Elburg, Marlina; Krohne, Nicole; Damaske, Detlef; Lisker, Frank (Tectonics, 2015)
Structural investigations in western Sør Rondane, eastern Dronning Maud Land (DML), provide new insights into the tectonic evolution of East Antarctica. One of the main structural features is the approximately 120 km long and several hundred meters wide WSW-ENE trending Main Shear Zone (MSZ). It is characterized by dextral high-strain ductile deformation under peak amphibolite-facies conditions. Crosscutting relationships with dated magmatic rocks bracket the activity of the MSZ between late Ediacaran to Cambrian times (circa 560 to 530 Ma). The MSZ separates Pan-African greenschist- to granulite-facies metamorphic rocks with “East African” affinities in the north from a Rayner-age early Neoproterozoic gabbro-tonalite-trondhjemite-granodiorite complex with “Indo-Antarctic” affinities in the south. It is interpreted to represent an important lithotectonic strike-slip boundary at a position close to the eastern margin of the East African-Antarctic Orogen (EAAO), which is assumed to be located farther south in the ice-covered region. Together with the possibly coeval left-lateral South Orvin Shear Zone in central DML, the MSZ may be related to NE directed lateral escape of the EAAO, whereas the Heimefront Shear Zone and South Kirwanveggen Shear Zone of western DML are part of the south directed branch of this bilateral system.
Keywords: Dronning Maud Land; geokronologi; geologi; geovitenskap; petrografi; tektonikk

Reconstruction of changes in the Weddell Sea sector of the Antarctic Ice Sheet since the Last Glacial Maximum - Hillenbrand, Claus-Dieter; Bentley, Michael J.; Stolldorf, Travis D.; Hein, Andrew S.; Kuhn, Gerhard; Graham, Alastair G.C.; Fogwill, Christopher J.; Kristoffersen, Yngve; Smith, James. A.; Anderson, John B.; Larter, Robert D.; Melles, Martin; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
The Weddell Sea sector is one of the main formation sites for Antarctic Bottom Water and an outlet for about one fifth of Antarctica's continental ice volume. Over the last few decades, studies on glacial–geological records in this sector have provided conflicting reconstructions of changes in ice-sheet extent and ice-sheet thickness since the Last Glacial Maximum (LGM at ca 23–19 calibrated kiloyears before present, cal ka BP). Terrestrial geomorphological records and exposure ages obtained from rocks in the hinterland of the Weddell Sea, ice-sheet thickness constraints from ice cores and some radiocarbon dates on offshore sediments were interpreted to indicate no significant ice thickening and locally restricted grounding-line advance at the LGM. Other marine geological and geophysical studies concluded that subglacial bedforms mapped on the Weddell Sea continental shelf, subglacial deposits and sediments over-compacted by overriding ice recovered in cores, and the few available radiocarbon ages from marine sediments are consistent with major ice-sheet advance at the LGM. Reflecting the geological interpretations, different ice-sheet models have reconstructed conflicting LGM ice-sheet configurations for the Weddell Sea sector. Consequently, the estimated contributions of ice-sheet build-up in the Weddell Sea sector to the LGM sea-level low-stand of ∼130 m vary considerably. In this paper, we summarise and review the geological records of past ice-sheet margins and past ice-sheet elevations in the Weddell Sea sector. We compile marine and terrestrial chronological data constraining former ice-sheet size, thereby highlighting different levels of certainty, and present two alternative scenarios of the LGM ice-sheet configuration, including time-slice reconstructions for post-LGM grounding-line retreat. Moreover, we discuss consistencies and possible reasons for inconsistencies between the various reconstructions and propose objectives for future research. The aim of our study is to provide two alternative interpretations of glacial–geological datasets on Antarctic Ice-Sheet History for the Weddell Sea sector, which can be utilised to test and improve numerical ice-sheet models.
Keywords: Antarctica; Cosmogenic nuclide surface exposure age dating; Deglaciation; Geomorphology; Glacial history; Ice Shelf; Ice sheet; Last Glacial Maximum; Radiocarbon dating; Sea level; Sørishavet; Weddellhavet; geologi; geomorfologi; glasiologi

A community-based geological reconstruction of Antarctic Ice Sheet deglaciation since the Last Glacial Maximum - Bentley, Michael J.; Ó Cofaigh, Colm; Anderson, John B.; Conway, Howard; Davies, Bethan; Graham, Alastair G.C.; Hillenbrand, Claus-Dieter; Hodgson, Dominic A.; Jamieson, Stewart S.R.; Larter, Robert D.; Mackintosh, Andrew; Smith, James A.; et al. (Reconstruction of Antarctic Ice Sheet Deglaciation (RAISED), 2014)
A robust understanding of Antarctic Ice Sheet deglacial history since the Last Glacial Maximum is important in order to constrain ice sheet and glacial-isostatic adjustment models, and to explore the forcing mechanisms responsible for ice sheet retreat. Such understanding can be derived from a broad range of geological and glaciological datasets and recent decades have seen an upsurge in such data gathering around the continent and Sub-Antarctic islands. Here, we report a new synthesis of those datasets, based on an accompanying series of reviews of the geological data, organised by sector. We present a series of timeslice maps for 20 ka, 15 ka, 10 ka and 5 ka, including grounding line position and ice sheet thickness changes, along with a clear assessment of levels of confidence. The reconstruction shows that the Antarctic Ice sheet did not everywhere reach the continental shelf edge at its maximum, that initial retreat was asynchronous, and that the spatial pattern of deglaciation was highly variable, particularly on the inner shelf. The deglacial reconstruction is consistent with a moderate overall excess ice volume and with a relatively small Antarctic contribution to meltwater pulse 1a. We discuss key areas of uncertainty both around the continent and by time interval, and we highlight potential priorities for future work. The synthesis is intended to be a resource for the modelling and glacial geological community.
Keywords: Antarktis; Modelling; deglasiasjon; geologi; glasiologi; innlandsis

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

Electrical structure beneath Schirmacher Oasis, East Antarctica: a magnetotelluric study - Murthy, D N; Veeraswamy, K; Harinarayana, T; Singh, U K; Santosh, M (Polar Research, 2013)
Maitri Station (70.76°S; 11.73°E) is located in Schirmacher Oasis, a coastal nunatak in north-central Dronning Maud Land covering an area of 35 km2. Here, we report results from the first magnetotelluric experiments and delineate the deep electrical conductivity structure under Schirmacher Oasis using the data acquired during the 24th Indian Antarctic Scientific Expedition. The magnetotelluric method has the advantage of shallow to deeper level coverage as the data acquisition covers a wide frequency band of 10-3103 Hz, permitting different penetration depths depending on the frequency and conductivity of the layer under investigation. The modelling results indicate the presence of a highly resistive (8000-10 000 ohm m) upper crust, which shows a lateral variation in thickness from 20 km (below site 6) in the east to 10 km (between sites 1 and 2) in the west. It is underlain by a less resistive (500-600 ohm m) lower crust. The highly resistive upper crustal structure supports the existing notion that western Dronning Maud Land is a stable, cratonic platform. Results of free-air gravity, seismic, geomagnetic and surface wave dispersion investigations in East Antarctica also indicate a cratonic-type crust. The results of our study allow us to identify a westward thinning of the upper crust with a marked boundary between sites 1 and 2. We also find evidence for the continuity of the Mozambique mobile belt in East Antarctica on the western side of Schirmacher Oasis. Keywords: Magnetotellurics; Schirmacher Oasis crustal structure; East Antarctica; Mozambique Belt; electrical conductivity.
Keywords: Dronning Maud Land; geofysikk; geologi; magnetotelluriske eksperimenter

The first men on the last continent – Carsten Egeberg Borchgrevink and the Southern Cross expedition, 1898 -1900 - Smelror, Morten (Fram forum, 2013)
Keywords: Antarktis; Carsten Egeberg Borchgrevink; Kapp Adare; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; første landgang; geologi; oppdagelsesreiser; overvintring

The oldest elasmosaurs (Sauropterygia, Plesiosauria) from Antarctica, Santa Marta Formation (upper Coniacian? Santonian-upper Campanian) and Snow Hill Island Formation (upper Campanian-lower Maastrichtian), James Ross Island - O'Gorman, José P (Polar Research, 2012)
Elasmosaurs are recorded for the first time in the Lachman Crags Member (Beta Member) of the Santa Marta Formation (lower Campanian) and in the Herbert Sound Member of the Snow Hill Island Formation (upper Campanian). These are the first elasmosaurids from James Ross Island, Antarctic Peninsula. These records greatly improve our knowledge of the taxonomic diversity of plesiosaurs of the Santa Marta Formation and Herbert Sound Member of the Snow Hill Island Formation, and extend the lower limit of the record of Elasmosauridae in Antarctica to the lower Campanian, making this the oldest record of an Antarctic elasmosaur. Keywords: Elasmosauridae; Antarctica; Late Cretaceous.
Keywords: Antarktis; geologi; paleontologi

The oldest plesiosaur (Reptilia, Sauropterygia) from Antarctica - Kellner, Alexander Wilhelm Armin; Simões, Tiago Rodrigues; Riff, Douglas; Grillo, Orlando; Romano, Pedro; Paula, Helder de; Ramos, Renato; Carvalho, Marcelo; Sayão, Juliana; Oliveira, Gustavo; Rodrigues, Taissa (Polar Research, 2011)
Antarctic plesiosaurs are known from the Upper Cretaceous López de Bertodano and Snow Hill Island formations (Campanian to upper Maastrichtian), which crop out within the James Ross Basin region of the Antarctic Peninsula. Here we describe the first plesiosaur fossils from the Lachman Crags Member of the Santa Marta Formation, north-western James Ross Island. This material constitutes the stratigraphically oldest plesiosaur occurrence presently known from Antarctica, extending the occurrence of plesiosaurians in this continent back to Santonian times (86.3-83.5 Mya). Furthermore, MN 7163-V represents the first plesiosaur from this region not referable to the Elasmosauridae nor Aristonectes, indicating a greater diversity of this group of aquatic reptiles in Antarctica than previously suspected. Keywords: James Ross Island; Antarctica; plesiosauria; Late Cretaceous; Museu Nacional.
Keywords: Antarktis; geologi; paleontologi; svaneøgler

Millennial scale evolution of the Southern Ocean chemical divide - Charles, Christopher D.; Pahnke, Katharina; Zahn, Rainer; Mortyn, P.G.; Ninnemann, Ulysses; Hodell, D.A. (Quaternary Science Reviews, 2010)
The chemical properties of the mid-depth and deep Southern Ocean are diagnostic of the mechanisms of abrupt changes in the global ocean throughout the late Pleistocene, because the regional water mass conversion and mixing help determine global ocean gradients. Here we define continuous time series of Southern Ocean vertical gradients by differencing the records from two high deposition rate deep sea sedimentary sequences that span the last several ice age cycles. The inferred changes in vertical carbon and oxygen isotopic gradients were dominated by variability on the millennial scale, and they followed closely the abrupt climate events of the high latitude Northern Hemisphere. In particular, the stadial events of at least the last 200kyr were characterized by enhanced mid-deep gradients in both δ13C (dissolved inorganic carbon) and δ18O (temperature). Interstadial events, conversely, featured reduced vertical gradients in both properties. The glacial terminations represented exceptions to this pattern of variability, as the vertical carbon isotopic gradient flattened dramatically at times of peak warmth in the Southern Ocean surface waters and with little or no corresponding change δ18O gradient. The available evidence suggests that properties of the upper layer of the Southern Ocean (Antarctic Intermediate Water) were influenced by an atmospherically mediated teleconnection to high latitude Northern Hemisphere.
Keywords: Sørishavet; geologi; oseanografi; paleoklimatologi

A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Glaciomarine sediments and suspended particulate matter, Weddell Sea Shelf, Antarctica - Elverhøi, Anders; Roaldset, Elen (Polar Research, 2010)
Keywords: NARE 1978/79; Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; sedimentologi; stratigrafi

Fluid infiltration, heat transport, and healing of microcracks in the damage zone of magmatic veins: Numerical modeling - Engvik, Lars; Stöckhert, Bernhard; Engvik, Ane K (Journal of Geophysical Research: Solid Earth, 2009)
Alteration halos with sharp boundaries are flanking pegmatitic veins in high-grade metamorphic and magmatic rocks of Dronning Maud Land, Antarctica. These halos are interpreted to represent the damage zone, formed as the wake of the process zone at the tip of the propagating magma-filled fracture and infiltrated by the fluid phase liberated from the crystallizing hydrous melt. On the basis of a set of assumptions, our numerical model explores the time scales of the infiltration processes, taking into account the combined effects of fluid flow, heat transfer, and temperature-dependent decay of interconnected porosity due to microcrack healing. Assuming an initial magma temperature of 700°C, a far field temperature in the host rock of 300°C, an initial porosity range of 0.5–2% in the damage zone, a permeability of 10−16 m2, and a pressure difference of 300 MPa, we find that the fluid infiltration into the damage zone proceeds within seconds to minutes and that the fluid flow contributes significantly to the heat transfer into the host rock. Assuming an initial microcrack aperture of 1 μm, the model predicts that the crack healing time scale is significantly longer than that of fluid infiltration in the case of thin veins with narrow damage zones; in this case, crack healing does not hinder fluid infiltration. Only for thick veins with high heat content and prolonged crystallization history does permeability become reduced by crack healing during progressive fluid infiltration. The results indicate that the formation of the alteration halos flanking pegmatitic veins may be a quasi-instantaneous process on geological time scales.
Keywords: Dronning Maud Land; geofysikk; geologi; mineralogi

A review of two decades (1986 2008) of geochronological work in Heimefrontfjella, and geotectonic interpretation of western Dronning Maud Land, East Antarctica - Jacobs, Joachim (Polarforschung, 2009)
During two decades (1986 - 2008) of geochronological work in Heimefrontfjella, nearly 130 geochronological ages were produced using a wide range of geochronological techniques. The ages fall into four broad age groups from Archaean to Cenozoic times, revealing a long and complex geological history. In general, Heimefrontfjella consists of Mesoproterozoic high grade basement related to the ∼1100 Ma Maud Belt. This basement is overlain by Permo-Carboniferous sedimentary rocks and Jurassic lavas. Archaean and Palaeoproterozoic detrital zircon ages are recorded from meta-sedimentary rocks probably characterizing the foreland of the Maud Belt. The protolith and metamorphic ages of the Mesoproterozoic Maud Belt fall into two groups. An older age group from ∼1200-1100 Ma is related to back-arc and island arc volcanism. High-grade metamorphism in the Maud Belt is dated between 1090-1060 Ma and is thought to reflect continent-continent collision, possibly related to the formation of Rodinia. Regional cooling to below 500-300 °C at ∼1010-960 Ma in part of the mountain range might indicate rifting of Rodinia. The eastern part of the mountain range is overprinted by the ∼600-500 Ma East African-Antarctic Orogen. The orogenic front of this major mobile belt is exposed in the study area as the Heimefront Shear Zone. East of this major lineament all Ar-Ar, K-Ar and Rb-Sr mineral ages are reset to ∼500 Ma. Initial Gondwana rifting affected the area at c. 180 Ma, when the Bouvet/Karroo mantle plume caused dynamic uplift of the area, followed by burial underneath up to 2 km of Jurassic lava. This led to tempering of the basement up to about 100 °C, as indicated by apatite fission track data. The lava pile underwent erosion in Cretaceous time, when renewed rifting affected the region. Latest tectonic movements might be related to Cenozoic ice loading related to the built up of the Antarctic ice sheet.
Keywords: Dronning Maud Land; ekspedisjoner; geokronologi; geologi; tektonikk

Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging

Apatite single-grain (U-Th)/He data from Heimefrontfjella, East Antarctica: Indications for differential exhumation related to glacial loading? - Emmel, Benjamin; Jacobs, Joachim; Crowhurst, P; Austegard, Atle; Schwarz-Schampera, Ulrich (Tectonics, 2008)
Single-grain (U-Th)/He ages from two profiles were used to reconstruct the post-Permian tectonic-thermal history of basement rocks in Heimefrontfjella, East Antarctica. The (U-Th)/He ages from one sample collected below the late Carboniferous/Early Permian sedimentary cover rocks indicate Jurassic–Early Cretaceous basement paleotemperatures of ∼40°–60°C due to post-Permian burial. Combined apatite fission track and (U-Th)/He analyses from samples of a profile in Sivorgfjella suggest a period of flexural-related tilting after ∼87 Ma. The timing was further constrained using forward and inverse models of the (U-Th)/He data. Model results indicate a Cenozoic phase of relatively rapid cooling from ∼40°C to surface temperatures. As the driving mechanism, we propose flexural isostatic rebound due to glacial load during the development of the intracontinental ice sheet in the hinterland of the Heimefrontfjella region.
Keywords: Antarktis; geologi; tektonikk; termokronologi

Early Palaeozoic orogenic collapse and voluminous late-tectonic magmatism in Dronning Maud Land and Mozambique: insights into the partially delaminated orogenic root of the East African–Antarctic Orogen? - Jacobs, Joachim; Bingen, Bernard; Thomas, Robert J; Bauer, Wilfried; Wingate, Michael T D; Feitio, Paulino (Geological Society, London, Special Publications, 2008)
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; tektonikk

Changes at Peter I Øy - Headland, Robert K (Polar Research, 2007)
Peter I Øy, a remote Norwegian territory, is one of the most rarely visited of the peri-Antarctic islands. Since the last Norwegian research visit, in 1987, approximately 10 tourist ships have been to the island, and about half of these have made landings. Where practical, reports have been sent to the Norwegian Polar Institute and other interested parties. I have made five visits, landing during four of them, while employed by Quark Expeditions to lecture on Antarctic history and geography aboard Kapitan Khlebnikov . My most recent visit, on 21 November 2006, demonstrated the continual geological erosion of the coast. In 2004 at Pingvinholet there was a splendid triple natural arch: the outer arch was formed by black basaltic deposits, and the inner one was capped by a stratum of red oxidized larva. The third arch was the result of a basalt flake slipping and propping itself against the middle column. The sea penetrated through all three arches so that it would have been possible, although reckless, to take a small boat through the largest of them. In late 2006, while sailing from South America to New Zealand near the Antarctic coast, I noted the entire inner section had collapsed. Only one large arch now remains and this no longer admits the sea. The collapse of both the cap of red larva and supporting pillar has formed a pile of rubble several metres above the sea.
Keywords: Peter I. Øy; geologi; turisme

Remembering Tore Gjelsvik (1916–2006) - Orheim, Olav (Polar Research, 2006)
Tore Gjelsvik, former director of the Norwegian Polar Institute, died at the beginning of this year. He is fondly remembered by a great many people. In this piece, Olav Orheim recalls the man and his key role in Norwegian polar activities. Orheim was head of Antarctic Research at the Norwegian Polar Institute in 1972–1993 and was the institute’s director from 1993 to 2005.
Keywords: Antarktis; Norsk Polarinstitutt; biografi; geologi; polarområdene

Taxonomic turnover and abundance in Cretaceous to Tertiary wood floras of Antarctica: implications for changes in forest ecology - Cantrill, David J.; Poole, Imogen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Based on the temporal distribution, abundance, and taxonomic composition of wood floras, four phases of vegetation development are recognized through the Cretaceous to Early Tertiary of the Antarctic Peninsula: (1) Aptian to Albian communities dominated by podocarpaceous, araucarian, and minor taxodiaceous/cupressaceous conifers with rare extinct gymnosperms (Sahnioxylon). (2) Progressive replacement of these communities in ?Cenomanian to Santonian times by angiosperms, most without modern analogues. (3) Increasing dominance of angiosperms becoming important both in terms of diversity and abundance towards the mid-Late Cretaceous. (4) Modernization of the flora during the Campanian to Maastrichtian with the extinction of earlier forms, appearance of the Nothofagaceae and diversification of associated elements. These patterns broadly follow trends seen in the leaf and palynological record but with some important differences. During the Cretaceous, conifer composition undergoes a change whereby Phyllocladoxylon-type woods increase relative to the older Podocarpoxylon forms. During the Paleocene to Eocene period, a marked extinction in wood types occurs associated with an increase in the abundance of nothofagaceous wood. Detailed examination of wood abundance and distributions from sections within Maastrichtian and Paleocene formations points to strong environmental control on taxonomic compositions. Similar differences are encountered when comparing coeval floras from different geographic regions and palaeoenvironments.
Keywords: Antarktis; flora; geologi; paleobotanikk; paleogeografi; paleontologi

Magma-driven hydraulic fracturing and infiltration of fluids into the damaged host rock, an example from Dronning Maud Land, Antarctica - Engvik, Ane K.; Bertram, Andreas; Kalthoff, Jörg F.; Stöckhert, Bernhard; Austrheim, Håkon; Elvevold, Synnøve (Journal of Structural Geology, 2005)
Excellent outcrops in Dronning Maud Land, Antarctica, provide unique insight into the mode and extent of fluid infiltration into metamorphic and plutonic rocks in the middle crust. The fluids are liberated from pegmatitic veins and give rise to alteration halos. In the alteration halos, the conspicuous change in colour is correlated with (1) hydration mineral reactions, and (2) high density of microcracks in quartz and feldspar exceeding that observed in the unaltered host rock by an order of magnitude. The field relations indicate that the veins originated as melt-driven hydraulic fractures, sealed by pegmatite and aplite crystallising from volatile-rich melts, with the alteration halo being the wake of the process zone formed at the tip of the propagating fractures. It is proposed that (1) the size of the alteration zone and the width of the vein are correlated, resulting in higher values of both these quantities for cracks propagating at higher velocities and consequently higher crack propagation toughnesses; (2) the damage zone is characterised by a transient state of high permeability which was short-lived due to rapid healing and sealing of microcracks; (3) the infiltration and retrogression of the high-grade rocks can be considered as a quasi-instantaneous process on geologic time scales with a duration of hours to weeks.
Keywords: Dronning Maud Land; geologi; petrologi

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

Antarktis: gamle gneiser og spektakulære granitter - Engvik, Ane K; Elvevold, Synnøve (Geo: energi & ressurser, 2004)
Keywords: Antarktis; Dronning Maud Land; geologi

Pan-African extension and near-isothermal exhumation of a granulite facies terrain, Dronning Maud Land, Antarctica - Engvik, Ane K.; Elvevold, Synnøve (Geological Magazine, 2004)
The Mühlig-Hofmann- and Filchnerfjella in central Dronning Maud Land, Antarctica, consist of series of granitoid igneous rocks emplaced in granulite and upper amphibolite facies metamorphic rocks. The area has experienced high-temperature metamorphism followed by near-isothermal decompression, partial crustal melting, voluminous magmatism and extensional exhumation during the later phase of the late Neoproterozoic to Cambrian Pan-African event. Remnants of kyanite–garnet–ferritschermakite–rutile assemblages indicate an early higher-pressure metamorphism and crustal overthickening. The gneisses experienced peak granulite facies temperatures of 800–900 °C at intermediate pressures. Breakdown of garnet + sillimanite + spinel-bearing assemblages to cordierite shows subsequent re-equilibration to lower pressures. An E–W foliation dominating the gneisses illustrates transposition of migmatites and leucocratic melts which evolved during the near-isothermal decompression. Occurrence of extensional shear bands and shear zones evolving from the ductile partial melting stage through semiductile towards brittle conditions, shows that the uplift persisted towards brittle crustal conditions under tectonic W/SW-vergent extension. Late-orogenic Pan-African quartz syenites intruded after formation of the main gneiss fabric contain narrow semiductile to brittle shear zones, illustrating that the extensional exhumation continued also after their emplacement. The latest record of the Pan-African event is late-magmatic fluid infiltration around 350–400 °C and 2 kbar. At this stage the Pan-African crust had undergone 15–20 km exhumation from the peak granulite facies conditions. We conclude that the later phase of the Pan-African event in central Dronning Maud Land is characterized by a near-isothermal decompression P–T path and extensional structures indicating tectonic exhumation, which is most likely related to a late-orogenic collapsing phase of the Pan-African orogen.
Keywords: Dronning Maud Land; geologi; petrologi

Holocene climate in the Atlantic sector of the Southern Ocean: Controlled by insolation or oceanic circulation? - Nielsen, Simon Harder Holm; Koç, Nalân; Crosta, Xavier (Geology, 2004)
The Holocene climate of the Southern Ocean is not well understood, mainly because of the lack of high-resolution reconstructions of ocean surface properties. Here we present a 12,500-yr-long, decadal-scale record of Holocene sea-surface temperatures and sea- ice presence from the Polar Front of the East Atlantic Southern Ocean. The record shows gradual climate change, with no abrupt Neoglacial cooling, and an unprecedented late Holocene warming. The dominant forcing factor appears to be precessional insolation; Northern Hemisphere summer insolation correlates to at least the early to middle Holocene climate trend. Spectral analysis reveals centennial-scale cyclic climate changes with periods of 1220, 1070, 400, and 150 yr. The record shows good correlation to East Antarctic ice cores and to climate records from South Georgia and Bunger Oasis. However, the record shows out-of-phase behavior with regard to climate records from the western Antarctic Peninsula and the Peru-Chile Current; such behavior hints at a climatic divide through Patagonia, the Drake Passage, and between West and East Antarctica.
Keywords: Antarktis; Sørishavet; geologi; havis; klimaendringer; paleoklimatologi

Evidence for orbitally controlled size variations of the East Antarctic Ice Sheet during the late Miocene - Grützner, J.; Rebesco, M.A.; Cooper, A.K.; Forsberg, C.F.; Kryc, K.A.; Wefer, G. (Geology, 2003)
Ocean Drilling Program Site 1165 penetrated drift sediments on the East Antarctic continental rise and recovered sediments from a low-energy depositional environment. The sediments are characterized by prominent alternations between a green to greenish-gray diatom-bearing hemipelagic facies and gray to dark gray hemiturbiditic facies. Our investigation of an upper Miocene section, using high-resolution color spectra, multisensor core logs, and X-ray fluorescence scans, reveals that sedimentation changes occur at Milankovitch orbital frequencies of obliquity and precession. We use this finding to derive an astronomical calibrated time scale and to calculate iron mass-accumulation rates, as a proxy for sediment-accumulation rates. Terrigenous iron fluxes change by as much as 100% during each obliquity cycle. This change and an episodic pattern of enhanced ice-rafted debris deposition during times of deglaciation provide evidence for a dynamic and likely wet-based late Miocene East Antarctic Ice Sheet (EAIS) that underwent large size variations at orbital time scales. The dynamic behavior of the EAIS implies that a significant proportion of the variability seen in oxygen isotope records of the late Miocene reflects Antarctic ice-volume changes.
Keywords: Antarktis; Sørishavet; geologi; glasiologi; maringeologi; paleoklimatologi

A 1.3-Myr palaeoceanographic record from the continental margin off Dronning Maud Land, Antarctica - Forsberg, Carl Fredrik; Løvlie, Reidar; Jansen, Eystein; Solheim, Anders; Sejrup, Hans Petter; Lie, Hans Erik (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
A 12.5 m long core was retrieved from the continental margin off Dronning Maud Land, Antarctica. Magnetostratigraphy, stable isotopes, 14C accelerator mass spectrometer and amino acid analyses indicate a continuous sediment record going back 1.3 Myr. Comparison of CaCO3 results with those from ODP Site 1089 and an index of North Atlantic Deep Water (NADW) influence in surface waters indicate that NADW upwelled along the Antarctic continental margin during the whole of this period. The mid-Pleistocene transition (1.0–0.6 Ma) was accompanied by an apparent decline in the NADW influence, and was followed by extended carbonate dissolution during the interglacials of marine isotope stages (MIS) 13 and 11. Less extensive periods of dissolution occur at the end of the interglacials younger than MIS 11. While interglacial dissolution is characteristic of the Pacific and Indian oceans, the carbon isotopes return to pre-transition values indicative of renewed NADW upwelling. The concentration of ice-rafted debris may reflect changes in the relative rate of interglacial sedimentation. It is speculated that the high ice rafted debris (IRD) concentrations during interglacials younger than 400 kyr may be due to a reduced relative sedimentation rate of other interglacial components whereas the low concentrations during interglacials before the mid-Pleistocene transition may be due to a higher relative sedimentation rate of these.
Keywords: Dronning Maud Land; Weddellhavet; geologi; magnetostratigrafi; oseanografi; paleoklimatologi; paleoseanografi; stabile isotoper

Magnitude scales for very local earthquakes. Application for Deception Island Volcano (Antarctica) - Havskov, Jens; Peña, José A; Ibáñez, Jesús M; Ottemöller, Lars; Martı́nez-Arévalo, Carmen (Putting Volcano Seismology in a Physical Context. In memory of Bruno Martinelli, 2003)
Different magnitude scales are calculated for a set of volcano-tectonic earthquakes recorded in Deception Island Volcano (Antarctica). The data set includes earthquakes recorded during an intense seismic series that occurred in January–February 1999, with hypocentral distances that range between 0.5 and 15 km. This data set is enlarged to include some regional earthquakes with hypocentral distances up to 200 km. The local magnitude scale, ML, fixed at a hypocentral distance of 17 km, is used as the reference for the other magnitude scales studied in the present work. ML is determined on a standard Wood–Anderson simulated trace assuming a gain of 2080. Maximum peak-to-peak amplitudes are measured on the vertical components of a short-period sensor. The Mw scale is calculated, in the vertical component, both for P and S waves. The attenuation correction of the ground motion displacement spectra is introduced using data from coda waves studied in the area. The comparison between ML values and Mw estimations indicates severe discrepancies between both values. A magnitude–duration scale is calibrated from the comparison between coda durations of the recorded events and their assigned local magnitude scales. In order to investigate the causes of the discrepancy between the ML and Mw values we analyze two possible error sources: a wrong coda Q value, or the effects of the near-surface attenuation that initially are not taken into account in the correction of the ground displacement spectra. The analysis reveals that the main cause of this discrepancy is the effect of the near-surface attenuation. The near-surface attenuation is also the cause of the determination of an anomalous spectral decay slope, after the corner frequency, and the determination of this corner frequency value. This near-surface attenuation, represented by κ, is estimated over the data set, obtaining an average value of 0.025. With this κ value, the Mw scale is recalculated using an automatic algorithm. The new Mw values are more consistent with the ML values, obtaining a relationship of Mw=0.78ML−0.02.
Keywords: Antarktis; Deceptionøya; geologi; vulkaner

Calcareous dinoflagellate associations and Maastrichtian–Tertiary climatic change in a high-latitude core (ODP Hole 689B, Maud Rise, Weddell Sea) - Hildebrand-Habel, Tania; Streng, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
The distribution of calcareous dinoflagellates has been analysed for the Maastrichtian–Miocene interval of Ocean Drilling Project Hole 689B (Maud Rise, Weddell Sea). The investigation thus represents a primary evaluation of the long-term evolution in high-latitude calcareous dinoflagellate assemblages during the transition from a relatively warm Late Cretaceous to a cold Neogene climate. Major assemblage changes during this interval occurred in characteristic steps: (1) an increase in relative abundance of tangentially structured species – particularly Operculodinella operculata – at the Cretaceous/Tertiary boundary; (2) a diversity decrease and several first and last appearances across the Middle–Late Eocene boundary, possibly attributed to increased climate cooling; (3) a diversity decrease associated with the dominance of Calciodinellum levantinum in the late Early Oligocene; (4) the reappearance and dominance of Pirumella edgarii in the Early Miocene, probably reflecting a warming trend; (5) monogeneric assemblages dominated by Caracomia spp. denoting strong Middle Miocene cooling. The results not only extend the biogeographic ranges of many taxa into the Antarctic region, but also indicate that the evolution of high-latitude calcareous dinoflagellate assemblages parallels the changing environmental conditions in the course of the Cenozoic climate transition. Therefore, calcareous dinoflagellates contribute to our understanding of the biotic effects associated with palaeoenvironmental changes and might possess the potential for reconstructing past conditions. The flora in the core includes one new taxon: Caracomia arctica forma spinosa Hildebrand-Habel and Streng, forma nov. Additionally, two new combinations are proposed: Fuettererella deflandrei (Kamptner, 1956) Hildebrand-Habel and Streng, comb. nov. and Fuettererella flora (Fütterer, 1990) Hildebrand-Habel and Streng, comb. nov.
Keywords: Sørishavet; Weddellhavet; geologi; klimaendringer; paleogeografi; paleoklimatologi; polarområdene

The making and unmaking of a supercontinent: Rodinia revisited - Meert, Joseph G.; Torsvik, Trond H. (Orogenic Belts, Regional and Global Tectonics: A Memorial Volume to Chris McAulay Powell, 2003)
During the Neoproterozoic, a supercontinent commonly referred to as Rodinia, supposedly formed at ca. 1100 Ma and broke apart at around 800–700 Ma. However, continental fits (e.g., Laurentia vs. Australia–Antarctica, Greater India vs. Australia–Antarctica, Amazonian craton [AC] vs. Laurentia, etc.) and the timing of break-up as postulated in a number of influential papers in the early–mid-1990s are at odds with palaeomagnetic data. The new data necessitate an entirely different fit of East Gondwana elements and western Gondwana and call into question the validity of SWEAT, AUSWUS models and other variants. At the same time, the geologic record indicates that Neoproterozoic and early Paleozoic rift margins surrounded Laurentia, while similar-aged collisional belts dissected Gondwana. Collectively, these geologic observations indicate the breakup of one supercontinent followed rapidly by the assembly of another smaller supercontinent (Gondwana). At issue, and what we outline in this paper, is the difficulty in determining the exact geometry of the earlier supercontinent. We discuss the various models that have been proposed and highlight key areas of contention. These include the relationships between the various ‘external’ Rodinian cratons to Laurentia (e.g., Baltica, Siberia and Amazonia), the notion of true polar wander (TPW), the lack of reliable paleomagnetic data and the enigmatic interpretations of the geologic data. Thus, we acknowledge the existence of a Rodinia supercontinent, but we can place only loose constraints on its exact disposition at any point in time.
Keywords: Antarktis; Dronning Maud Land; geologi; paleogeografi

A geochronological and geochemical study of rocks from Gjelsvikfjella, Dronning Maud Land, Antarctica—implications for Mesoproterozoic correlations and assembly of Gondwana - Paulsson, Oskar; Austrheim, Håkon (Precambrian Research, 2003)
The Jutulsessen nunataks (72°00′S; 2°30′E), Gjelsvikfjella, Dronning Maud Land (DML), consist mainly of migmatites of two types. A heterogeneous banded amphibolite facies gneisses and a more homogeneous part. In the more homogeneous part, partial melts form along axial planes to tight folds. Numerous pegmatitic dykes occur in both migmatites. The homogeneous part of the migmatite has a granodiorite composition. It displays the depletion of Nb–Ta typical for rocks from destructive plate margins and a strongly fractionated REE pattern, specially in LREE (La/Lu ratios varying between 500 and 800). SIMS dating of zircon from the homogeneous migmatite and two pegmatite dykes resulted in two age groups. A concordant age of 1163±6 Ma is calculated from zircon crystals with no rim/core structure and from cores from structurally complex crystals. This age represents the age of the protolith of the migmatite. A Cambrian age of 504±6 Ma is obtained from zircon rims and from sector-zoned zircons. This age represent the time of migmatisation. Sm–Nd depleted mantle model ages range from 1390 to 1770 Ma and suggest that the protolith to the migmatites contained components of older crust (pre-1163 Ma). An igneous complex consisting of a syenite plug (Stabben syenite), gabbroic rocks and aplitic dykes intrudes the metamorphic complex. The syenite and the aplitic dykes are neither deformed nor migmatised or penetrated by pegmatitic dykes. These rocks have elevated LREE and LILE concentrations with an La/Lu ratio of 450 and an Nb–Ta trough. The gabbroic rocks range in composition from melagabbro to monzogabbro and host numerous pegmatitic dykes. SIMS zircon U–Pb data from the Stabben syenite give an age of 500±8 Ma. This age is regarded as the intrusive age of the Stabben syenite. By the single zircon–Pb evaporation method an age of 495±14 Ma is obtained from the aplitic dykes. Sm–Nd depleted mantle model ages between 1800 and 2220 Ma indicate that the dykes formed from a Paleoproterozoic source. A Mesoproterozoic volcanic arc setting of DML and a correlation with the Natal Province, as suggested by several authors, is supported by data in this study. The studied area has consequently been a part of the Kaapvaal/Kalahari craton since Mesoproterozoic time. The Cambrian migmatisation and the intrusions are interpreted as a result of post-collision activity related to the collision between the Kalahari craton and the combined block of Antarctica and Australia during the final assembly of Gondwana. This collision is suggested to be included in the Kuunga Orogeny introduced by Meerat and Van der Voo [J. Geodynam. 23 (1997) 223].
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geokronologi; geologi; nunataker; petrologi

Radionuclides deposition over Antarctica - Pourchet, Michel; Magand, Olivier; Frezzotti, Massimo; Ekaykin, Alexey A.; Winther, Jan Gunnar (Journal of Environmental Radioactivity, 2003)
A detailed and comprehensive map of the distribution patterns for both natural and artificial radionuclides over Antarctica has been established. This work integrates the results of several decades of international programs focusing on the analysis of natural and artificial radionuclides in snow and ice cores from this polar region. The mean value (37±20 Bq m−2) of 241Pu total deposition over 28 stations is determined from the gamma emissions of its daughter 241Am, presenting a long half-life (432.7 yrs). Detailed profiles and distributions of 241Pu in ice cores make it possible to clearly distinguish between the atmospheric thermonuclear tests of the fifties and sixties. Strong relationships are also found between radionuclide data (137Cs with respect to 241Pu and 210Pb with respect to 137Cs), make it possible to estimate the total deposition or natural fluxes of these radionuclides. Total deposition of 137Cs over Antarctica is estimated at 760 TBq, based on results from the 90–180° East sector. Given the irregular distribution of sampling sites, more ice cores and snow samples must be analyzed in other sectors of Antarctica to check the validity of this figure.
Keywords: Antarktis; geofysikk; geologi; glasiologi; radioaktivitet

The mid-Pliocene (4.3–2.6 Ma) benthic stable isotope record of the Southern Ocean: ODP Sites 1092 and 704, Meteor Rise - Andersson, Carin; Warnke, Detlef A.; Channell, James E.T.; Stoner, Joseph S.; Jansen, Eystein (Palaeogeography, Palaeoclimatology, Palaeoecology, 2002)
We present mid-Pliocene (4.3–2.6 Ma) benthic stable oxygen and carbon isotope data from Ocean Drilling Program Site 1092 (ODP Leg 177) drilled in the sub-Antarctic sector of the Southern Ocean. The results are compared with the stable isotope results from nearby Site 704 (ODP Leg 114). Oxygen isotope data show that minimum values are about 0.5‰ less than those of the Holocene, which is consistent with the results from Site 704, indicating only minor deglaciation of Antarctica during the studied interval. Oxygen isotope data from both Site 1092 and Site 704 are slightly higher relative to Pacific values during several intervals which could be related to the contribution of warm, saline North Atlantic Deep Water (NADW). Comparisons of benthic carbon isotope gradients between sites located in the North Atlantic, sub-Antarctic sector of the Southern Ocean, and Pacific indicate that at times, the gradient between the Southern Ocean and the Pacific evolved differently than the Atlantic–Pacific gradient. This suggests that variations in NADW strength alone might not be responsible for the observed carbon isotope values in the Southern Ocean.
Keywords: Sørishavet; geologi; oseanografi; paleomagnetisme; paleontologi; stabile isotoper

Rapid climate shifts in the southern African interior throughout the Mid to Late Holocene - Lee-Thorp, Julia; Holmgren, Karin; Lauritzen, Stein Erik; Linge, Henriette; Moberg, Anders; Partridge, Timothy C; Stevenson, Chris; Tyson Peter D. (Geophysical Research Letters, 2001)
A detailed climate proxy record based on δ18O, δ13O, and grey index of a well-dated stalagmite from Cold Air Cave in the Makapansgat Valley of north-eastern South Africa suggests that regional precipitation, temperatures and vegetation oscillated markedly and rapidly over the last ∼6500 years on centennial and multi-decadal scales. The mid-Holocene prior to 5200 years ago was humid and warm. A fundamental transition occurred 3200 years ago, leading to drier and cooler conditions that culminated at 1750 AD. Comparisons with ice core records suggest synchronous changes implicating rapid global teleconnections.
Keywords: Antarktis; arkeologi; geografi; geologi; klimaendringer; klimatologi; paleontologi

Growing Gondwana and Rethinking Rodinia: A Paleomagnetic Perspective - Meert, Joseph G. (Gondwana Research, 2001)
The formation of Gondwana during the late Neoproterozoic to early Cambrian times (550-530 Ma) was traditionally viewed as the welding of two, more or less contiguous, Proterozoic continental masses called East and West Gondwana. The notion of a united West Gondwana is no longer tenable as a wealth of geochronologic and structural data indicate major orogenesis amongst its constituent cratons during the final stages of greater Gondwana assembly. The idea that East Gondwana may also have formed through the amalgamation of a collage of cratonic nuclei during the Cambrian is controversial. Recent paleomagnetic, geochronologic and structural data from elements of East Gondwana indicate that its formation may have extended well into Cambrian time. Thus, the terms ‘East’ and ‘West’ Gondwana may be relegated to convenient geographical terms rather than any connotation of tectonic coherence during the Proterozoic. In addition, the paleomagnetic data also challenge the conventional views of the Neoproterozoic supercontinent Rodinia and the SWEAT fit. Alternative variants including Protopangea and AUSWUS are not supported by paleomagnetic data during the interval 800–700 Ma.
Keywords: Antarktis; geokronologi; geologi; paleomagnetisme

Geochronologic evidence for Early Cretaceous volcanic activity on Barton Peninsula, King George Island, Antarctica - Kim, Hyeoncheol; Ik Lee, Jong; Young Chose, Moon; Cho, Moonsup; Zheng, Xiangshen; Sang, Haiquing; Qiu, Ji (Polar Research, 2000)
Ages of six volcanic and plutonic rocks on Barton Peninsula, King George Island, were determined using 40Ar/39Ar and K-Ar isotopic systems. The 40Ar/39Ar and K-Ar ages of basaltic andesite and diorite range from 48 My to 74 My and systematically decrease toward the upper stratigraphic section. Two specimens of basaltic andesite which occur in the lowermost sequence of the peninsula, however, apparently define two distinct plateau ages of 52-53 My and 119-120 My. The latter is interpreted to represent the primary cooling age of basaltic andesite, whereas the former is interpreted as the thermally-reset age caused by the intrusion of Tertiary granitic pluton. The isochron ages calculated from the isotope correlation diagram corroborate our interpretation based on the apparent plateau ages. It is therefore likely that volcanism was active during the Early Cretaceous on Barton Peninsula. When the K-Ar ages of previous studies are taken into account with our result, the ages of basaltic andesite in the northern part of the Barton Peninsula are significantly older than those in the southern part. Across the north-west-south-east trending Barton fault bounding the two parts, there are significant differences in geochronologic and geologic aspects.
Keywords: Antarktis; geokronologi; geologi; vulkaner

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Flood Basalts of Vestfjella: Jurassic Magmatism Across an Archaean–Proterozoic Lithospheric Boundary in Dronning Maud Land, Antarctica - Luttinen, Arto V.; Furnes, Harald (Journal of Petrology, 2000)
Continental flood basalts (CFBs) of Jurassic age make up the Vestfjella mountains of western Dronning Maud Land and demonstrate an Antarctic extension of the Karoo large igneous province. A detailed geochemical study of the 120-km-long Vestfjella range shows the CFB suite to consist mainly of three intercalated basaltic rock types designated CT1, CT2 and CT3 (chemical types 1, 2 and 3) that exhibit different incompatible trace element ratios. CT1 and CT2 of north Vestfjella record wide ranges of Nd and Sr isotopic compositions with initial εNd and εSr ranging from +7·6 to −16·0 and −16 to +65, respectively. The southern Vestfjella is dominated by CT3 with near-chondritic εNd (+2·0 to −4·1) and εSr (−11 to +19). A volumetrically minor suite of ocean island basalt (OIB-)like CT4 dykes (εNd +3·6, εSr +1) cuts the lava sequence in north Vestfjella. The pronounced isotopic differences suggest different magmatic plumbing systems for the heterogeneous CT1 and CT2 suites and the relatively homogeneous CT3 lavas. This is further supported by the palaeoflow directions, which point to major source regions to the north (CT1 and CT2) and east (CT3) of Vestfjella. These source regions can be associated with two contemporaneous major lithospheric thinning zones that permitted magma emplacement and controlled the melting of upper-mantle sources in the Jurassic Dronning Maud Land. The CT1 and CT2 magmas utilized the northern zone of thinning and were emplaced into the 3 Ga Grunehogna craton, whereas the CT3 magmas were emplaced through thinned Proterozoic Maud Belt lithosphere. Trace element and isotopic studies of the identified magma types reveal a complex history of fractionation and contamination at different lithospheric levels. All extrusive rock types show evidence of crustal contamination but this had rather small impact on their diagnostic trace element ratios. Much stronger overprint, in the CT1 and CT2 suites, resulted from contamination with veined Archaean lithospheric mantle, which produced wide ranges of isotopic and highly incompatible element ratios. CT3, in turn, does not show evidence of interaction with the Proterozoic lithospheric mantle. The high-εNd endmembers of CT1, CT2 and CT3 probably closely resemble uncontaminated mantle-derived magmas and indicate three different mantle sources. The CT2 primary magmas were derived from light rare earth element (LREE)-depleted, slightly large ion lithophile element (LILE)-enriched sources, whereas data on the volumetrically preponderant CT1 and CT3 point to variably LREE-enriched, strongly LILE-enriched sources. The sources of CT1, CT2 and CT3 may record large-scale lateral heterogeneity generated by subduction-contamination of the Gondwanan upper mantle. The OIB-like CT4 dykes probably reflect asthenospheric heterogeneities that were unrelated to the proposed subduction-contamination.
Keywords: Dronning Maud Land; geokjemi; geologi; petrografi; petrologi

Subglacial topography of Jutulstraumen outlet glacier, East Antarctica, mapped from ground-penetrating radar, optical and interferometric synthetic aperture radar satellite data - Melvold, Kjetil; Rolstad, Cecilie Eie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2000)
Keywords: Antarktis; geologi; glasiologi; isstrøm; topografi

The Antarctic contribution to Holocene global sea level rise - Ingólfsson, Ólafur; Hjort, Christian (Polar Research, 1999)
The Holocene glacial and climatic development in Antarctica differed considerably from that in the Northern Hemisphere. Initial deglaciation of inner shelf and adjacent land areas in Antarctica dates back to between 10-8 Kya, when most Northern Hemisphere ice sheets had already disappeared or diminished considerably. The continued deglaciation of currently ice-free land in Antarctica occurred gradually between ca. 8-5 Kya. A large southern portion of the marine-based Ross Ice Sheet disintegrated during this late deglaciation phase. Some currently ice-free areas were deglaciated as late as 3 Kya. Between 8-5 Kya, global glacio-eustatically driven sea level rose by 10-17m, with 4-8 m of this increase occurring after 7 Kya. Since the Northern Hemisphere ice sheets had practically disappeared by 8-7 Kya, we suggest that Antarctic deglaciation caused a considerable part of the global sea level rise between 8-7 Kya, and most of it between 7-5 Kya. The global mid-Holocene sea level high stand, broadly dated to between 8-4 Kya, and the Littorina-Tapes transgressions in Scandinavia and simultaneous transgressions recorded from sites e.g. in Svalbard and Greenland, dated to 7-5 Kya, probably reflect input of meltwater from the Antarctic deglaciation.
Keywords: Antarktis; geologi; glasiologi; havnivåstigning; innlandsis; paleoglasiologi; polarområdene

Petrogenesis of the volcanic suite of Bouvetøya (Bouvet Island), South Atlantic - Prestvik, Tore; Goldberg, Steven; Goles, Gordon G. (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1999)
Whole rock and mineral compositions of volcanic rocks collected during the Norwegian Polarsirkel expedition (1978/79) to the volcanic istand of Bovetøya (close to the Bouvet Triple Junction) are discussed and compared with previously published data from the island. The rock types, hawaiite, benmoreite, and peralkaline trachyte and rhyolite (comendite) are related to each other by crystal fractionation processes. The trace element and radiogenic isotope signatures displayed by the Bouvetøya rocks are those of a moderately enriched oceanic island suite. On several isotope plots Bouvetøya rocks fall on or close to mixing lines between the euriched EM-l and HIMU mantle components. Mixing between depleted morb mantle (DMM) and euriched components is not likely. Thus, Bouvetøya displays a typical plume signature.
Keywords: Bouvetøya; M/V Polarsirkel; NARE 1978/79; geokjemi; geologi; petrologi

Convergent flow of ice within the Astrolabe subglacial basin, Terre Adélie, East Antarctica: an hypothesis derived from numerical modelling experiments - Siegert, Martin J; Glasser, Neil F (Polar Research, 1997)
Keywords: Antarktis; geologi; geomorfologi; glasiologi; innlandsis; subglasial innsjø

Rock mapping of glaciated areas by satellite image processing - Salvini, Francesco; Della Maggiore, Roberto; Fortunati, Luciano; Mazzarini, Francesco (Polar Research, 1994)
Keywords: Antarktis; geologi; polarområdene; satellitt bilder

Granulites and garnet–cordierite gneisses from Dronning Maud Land, Antarctica - Bucher-Nurminen, Kurt; Ohta, Yoshihide (Journal of Metamorphic Geology, 1993)
The central sector of Mühlig-Hofmannfjellet (3°E/71°S) in western Dronning Maud Land (East Antarctic shield) is dominated by large intrusive bodies of predominantly orthopyroxene-bearing quartz syenites (charnockites). Metasedimentary rocks are rare; however, two distinct areas with banded gneiss–marble–quartzite sequences of sedimentary origin were found during the Norwegian Antarctic Research Expedition NARE 1989/90. Cordierite-bearing metapelitic gneisses from two different localities contain the characteristic mineral assemblage: cordierite + garnet + biotite + K-feldspar + plagioclase + quartz ± sillimanite ± spinel. Thermobarometry indicates equilibration conditions of about 650°C and 4 kbar. Associated orthopyroxene–garnet granulites, on the other hand, revealed pressures of about 8 kbar and temperatures of 750°C. The earlier granulite facies metamorphism is not well preserved in the cordierite gneisses as a result of excess K-feldspar combined with interaction with an H2O-rich fluid phase, probably released by the cooling intrusives. These two features allowed the original high-grade K-feldspar + garnet assemblages to recrystallize as cordierite–biotite–sillimanite gneisses, completely re-equilibrating them. Phase relationships indicate that the younger metamorphic event occurred in the presence of a fluid phase that varied in composition between the lithologies.
Keywords: Dronning Maud Land; NARE 1989/90; geokjemi; geologi

The geology and age of Peter I Øy, Antarctica - Prestvik, Tore; Duncan, Robert A (Polar Research, 1991)
The island Peter I Oy is located in the Bellinghausen Sea 400 km off the coast of West Antarctica. It is situated at the transition between oceanic and contintental crust close to a former transform fault, the Tharp fracture zone. The island is completely volcanic, consisting of predominantly alkali basalt and hawaiite and some more evolved rocks. Sampling done by the Aurora expedition in 1987 has made dating and detailed petrological studies possible. The island appears to be much younger (< 0.5 Ma) than previously believed. However, the volcanic activity responsible for this oceanic island may have lasted for 10-20 Ma. Volcanic activity at the island thus took place at the same time as post-subduction rift-related volcanism took place along the Antarctic Peninsula and in Marie Byrd Land. However, the petrologic data indicate that this may be coincidental and that the Peter I Oy activity is independent and related to transtensional rifting along the Tharp fracture zone.
Keywords: Peter I. Øy; geologi; petrologi

Geology of Gjelsvikfjella and western Mühlig-Hofmannfjella, Dronning Maud Land, east Antarctica - Ohta, Yoshihide; Tørudbakken, Bjørn; Shiraishi, Kazuyuki (Polar Research, 1990)
As a part of the Norwegian Antarctic Research Expedition 1984/85, geological mapping was performed in Gjelsvikfjella and western Muhlig-Hofmannfjella, Dronning Maud Land. The northern part of Gjelsvikfjella is dominated by the Jutulsessen metasupracrustals which have been intruded by a major gabbroic body and several generations of dykes. To the south the metasupracrustals gradually transform into the Risemedet migmatites. In western Muhlig-Hofmannfjella the bedrock is dominated by the large Svarthamaren Charnockite batholith. The batholith is bordered by the Snotoa metamorphic complex outcropping to the south and west in Muhlig-Hofmannfjella and it is characterized by a high content of partly assimilated country rock inclusions. Mineral paragenesis and geothermometry/geobarometry suggest a two-stage tectonothermal-igneous history with an initial intermediate pressure, upper amphibolite to granulite facies metamorphism followed by high temperature transformations related to the charnockite intrusion. The age of the initial tectonothermal event is probably about 1,100 Ma. Geochronological work in the present study (Rb/Sr whole rock) gave an age of 500 +/- 24 Ma for the Svarthamaren Charnockite, interpreted to record the age of crystallization. Late brittle faulting and undeformed dolerite dykes outcropping in Jutulsessen are believed to be related to Mesozoic crustal stretching in the Jutulstraumen-Pencksokket Rift Zone to the west.
Keywords: Dronning Maud Land; NARE 1984/85; geologi

Petrology of Peter I Øy (Peter I Island), West Antarctica - Prestvik, Tore; Barnes, Calvin G; Sundvoll, Bjørn; Duncan, Robert A (Journal of volcanology and geothermal research, 1990)
Peter I Øy is located in the Bellinghausen Sea, 400 km NE of Thurston Island, West Antarctica. It is a Pleistocene volcanic island situated adjacent to a former tranform fault on the continental rise of the presently passive margin between the Pacific and Antarctica. New K-Ar age determinations ranging from 0.1 to 0.35 Ma show that the volcanism responsible for this island took place at the same time as post-subduction, rift-related volcanism occurred in the nearby Marie Byrd Land and the Antarctic Peninsula. The rocks of the island are alkalic basalt and hawaiite, benmoreite and trachyte. The basic tocks typically contain phenocrysts of olivine (Fo61–84), diopsidic augite, and plagioclase (ca. An60). Small xenoliths are present and consist of mantle-type spinel lherzolite, cumulate clinopyroxenite and gabbro and felsic inclusions that consist of medium-grained strained quartz, plagioclase, and abundant colorless glass. Chemically, the basic rocks are characterized by rather high MgO (7.8–10.2 wt.%) and TiO2 (3.1–3.7 wt.%) and relatively low CaO (8.4–9.5 wt.%) contents. They have steep REE patterns, [(La/Yb)N = 20] with HREE only 5 x chrondrite. Y and Sc are almost constant at relatively low levels. Compatible trace elements such as Ni and Cr show considerable variation (190–300 and 150–470 ppm, respectively.), whereas V shows only little variation. Sr and Nd isotope ratios vary slightly with 87Sr/86Sr averaging 0.70388 and 143Nd/144Nd 0.512782, both typical for ocean island volcanism. Lead isotope ratios are consistently high in basalts; 206Pb/204Pb = 19.194, 207Pb/204Pb = 15.728 and 208Pb/204Pb = 39.290, whereas benmoreïte is somewhat less radiogenic. Oxygen isotope analyses average ‰ . Incompatible trace elements vary by a factor of 1.5–2.0 within the range of the basic rocks. It is proposed that the incompatible trace-element variations represent different degrees (<10%) of partial melting, and that these melts were later modified by minor ( ‰ ) olivine and spinel fractionation. The very small variation in Y (and Sc) and the very fractionated REE pattern indicate that the source had an Y- and HREE-rich residual phase, most probably garnet. Furthermore, it is suggested that the source was slightly hydrous and that melting took place at 18–20 kbar. Trachyte was derived by multiphase fractionation of ne-normative basalts, and benmoreite from hy-normative parental liquids. The rocks of Peter I Øy are generally of the same type and age as those outcropping in extensional regimes on the nearby continent, and therefore, these occurrences may be related to each other in some way. However, the Peter I Øy rocks are considerably more radiogenic in strontium and less radiogenic in neodymium than the rocks of the Antarctic Peninsula and Marie Byrd Land. Possible explanations are that Peter I Øy represent asthenospheric hot spot activity, or transtensional rifting as subduction ceased.
Keywords: Peter I. Øy; geologi; petrologi

Late Quaternary ice-surface fluctuations of Beardmore Glacier, Transantarctic Mountains - Denton, George H; Bockheim, James G; Wilson, Scott C; Leide, James E; Andersen, Björn G (Quaternary Research, 1989)
Former longitudinal profiles of Beardmore Glacier, an outlet through the Transantarctic Mountains, constrain polar plateau elevations near the center of Antarctica and ice-shelf grouding in the southern Ross Embayment. Three gravel drift sheets of late Quaternary age occur alongside Beardmore Glacier. Plunket drift, the youngest, is parallel to and 7–30 m above the present ice surface. The upper limit of Beardmore drift, intermediate in age, is within 35–40 m of the present ice surface near the polar plateau but about 1100 m above the present ice surface near the glacier mouth. The upper limit of Meyer drift, the oldest, is parallel to and 30–50 m above Beardmore drift. From correlation with numerically dated drifts farther north, we assign an early Holocene age to Plunket drift, a late Wisconsin age to Beardmore drift, and an age of marine isotope Stage 6 to Meyer drift. By our age model, Beardmore Glacier was close to current elevations in its upper reaches and thickened considerably in its middle and lower reaches during the last two global glaciations represented by Beardmore and Meyer drifts. Most likely, grounded ice in the southern Ross Embayment caused such thickening of Beardmore Glacier almost to the polar plateau. A concomitant decline in precipitation is implied by ice-cap retreat on the nearby Dominion Range and is consistent with little change of upper Beardmore Glacier. Ice-shelf grounding most likely resulted from lowered sea level and/or basal melting. Lower than present precipitation was probably caused by colder air temperatures and more-distant open water. The Plunket profile records Holocene ice-surface lowering from increased surface ablation, decreased ice flow, or grounding-line recession.
Keywords: Antarktis; geologi

Anomalous palaeomagnetic directions in a Mesozoic basaltic dyke; arguments for fault-induced remagnetization - Løvlie, Reidar; Mitchell, John (Physics of the earth and planetary interiors, 1989)
Anomalously steep palaeomagnetic directions from the central part of an ∼ 5 m wide basaltic dyke from Fossilryggen, East Antarctica, suggest a Recent to late Tertiary age for its remanent magnetization, in conflict with KAr isotope ages of 162 ± 4 and 217 ± 3 Ma obtained from the central and slickenside margins respectively. Three neighbouring basaltic intrusions carry stable magnetizations whose directions (mean D, 23°; mean I, −40° and pole position, 38°N, 40°E) accord with previously obtained Mesozoic results from lava flows in the Vestfjella basalt province, East Antarctica. Rock magnetic properties do not discriminate between the different dykes, and it is proposed that the anomalous directions represent spot-readings of the geomagnetic field which arise from complete remagnetization during a period of faulting in Recent to late Tertiary times.
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; geofysikk; geologi

Former extension of the East Antarctic Ice Sheet - Lundqvist, Jan (Polar Research, 1989)
Keywords: Antarktis; geologi; glasiologi; innlandsis

Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Evidence for deuteric magnetization in hydrothermally altered Mesozoic basaltic rocks from East Antarctica - Løvlie, Reidar (Physics of the earth and planetary interiors, 1988)
Mesozoic basaltic lavas and dykes from Vestfjella, East Antarctica, are dominated by well-grouped, single-component palaeomagnetic directions of normal polarity. Reversed magnetizations, heavily overprinted by normal polarity components, were encountered in a few lava flows and dykes. Only thermal demagnetization was successful in separating tight distributions of reversed polarity directions, interpreted to represent a deuteric magnetization. The region has been exposed to regional hydrothermal alteration to the epidote/prehnite metamorphic facies (T ≈ 300°C). Titanomagnetite grains in high-temperature oxidation classes II–III show alteration features typical for hydrothermally altered basalts; partial to complete replacement of both ilmenite and magnetite to sphene is common in the most altered rocks, which also exhibit varying degrees of decomposition of the opaque minerals. The lavas display two major, but distinctly different, thermomagnetic curves; the ‘kink’ type, previously reported from rocks exposed to the epidote metamorphic facies, and curves dominated by a paramagnetic contribution defining a magnetite Curie point. It is concluded that the basalts have retained palaeomagnetic directions acquired during the deuteric cooling phase, implying that granulation/sphene formation and Fe depletion of decomposed titanomagnetite grains in classes II–III do not necessarily cause complete remagnetization or the acquisition of significant secondary remanent magnetizations.
Keywords: Dronning Maud Land; geofysikk; geokjemi; geologi

Geochemistry of basalt lavas from Vestfjella and adjacent areas, Dronning Maud Land, Antarctica - Furnes, Harald; Vad, Erik; Austrheim, Håkon; Mitchell, John G.; Garmann, Leif B. (Lithos, 1987)
K-Ar ages, major- and trace-element compositions, and Sr-isotope data are presented for basalt lavas from Vestfjella, Dronning Maud Land, Antarctica. The new conventional K-Ar age data have yielded ages from 171 ± 2 to 695 ± 11 Ma, but the youngest (i.e. Middle Jurassic) ages are preferred. Mineralogical and chemical data show that the majority of the basalts are tholeiites. Petrographic mixing calculations, REE modelling, and the Sr isotope data suggest that they were derived by partial melting of garnet-free lherzolites with variable REE patterns, and subsequently modified by fractionation of olivine, Ca-rich pyroxene and plagioclase. Incompatible trace-element data from nearby Middle Jurassic basalt lavas (from Kirwanryggen and Heimefrontfjella) suggest a different source and REE modelling indicates generation from garnet lherzolites.
Keywords: Dronning Maud Land; NARE 1976/77; geokjemi; geologi; mineralogi; paleontologi; petrografi

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40^primeS and long. 10°W, lat. 69°20^primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Snorre til Sydpolen: 38 dager på isen (Status (Statoil), 1984)
Keywords: Dronning Maud Land; ekspedisjoner; geologi

Petrology and geochemistry of Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica - Furnes, Herald; Neumann, Else-Ragnhild; Sundvoll, Bjørn (Lithos, 1982)
Mineral and whole rocks analyses of 12 Jurassic basalt dykes from Vestfjella, Dronning Maud Land, Antarctica, are presented, and their genesis discussed. On the basis of major oxides and norms the basalts may be classified as olivine and quartz tholeiites. Plotted in the Plag Cpx (Opx + 4Q) and Ol Plag Q projections, the compositions are most compatible with fractional crystallization of olivine, clinopyroxene and plagioclase from a basalt liquid at very low pressure. The ratios between strongly incompatible elements such as Rb, Cs, Zr, Hf, Ta and Th vary considerably, and petrographic mixing calculations give poor fits with respect to Rb, Cs, Ta, Th and light REE. Initial 87Sr/86 Sr ratios range between 0.70347 and 0.70687, and show no correlation with Rb/Sr or any other SIE ratios. The trace element and Sr isotope data thus do not suggest any simple cogenetic petrogenetic model. It is concluded that the basalt melts most plausibly have been contaminated by, or mixed with anatectic melts of crustal material, rather than reflecting mantle heterogeneity.
Keywords: Dronning Maud Land; geokjemi; geologi; petrologi

The Continental Margin of Queen Maud Land/Antarctica: Seismic Sequences, Structural Elements and Geological Development - Hinz, Karl; Krause, W (Geologisches Jahrbuch. Reihe E, Geophysik, 1982)
Keywords: Dronning Maud Land; geologi; kontinentalmargin; seismologi

Basic volcanic rocks and tectonic setting. A discussion of the Zr-Ti-Y discrimination diagram and its suitability for classification purposes - Prestvik, Tore (Lithos, 1982)
Keywords: Bouvetøya; forskning; geologi; tektonikk; vulkaner

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica - Løvlie, Reidar (Geophysical Journal of the Royal Astronomical Society, 1979)
Thermal and alternating field demagnetization of oriented samples of Mesozoic lava flows (200–230 Myr) and dykes (154–172 Myr) collected from seven nunataks within the Vestfjella region, Dronning Maud Land, revealed stable directions of magnetization of normal and reverse polarity. Directional distributions of both polarities define tight groups along the same palaeomagnetic axis. Depending on whether the regional westward dip of the lava flows originated prior to, or after the intrusive igneous phase, two or one, respectively, palaeomagnetic pole(s) can be estimated. Both poles, however, are in general accord with previous Mesozoic poles from East Antarctica.
Keywords: Dronning Maud Land; NARE 1976/77; geofysikk; geologi

Basaltene i Vestfjella og Gondwanalands historie - Furnes, Harald (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geokjemi; geologi; petrologi

Hva den fossile magnetiseringen i Vestfjella kan fortelle - Løvlie, Reidar (Naturen, 1978)
Keywords: Dronning Maud Land; NARE 1976/77; ekspedisjoner; forskning; geologi; jordmagnetisme

Om Antarktis, isfjell og havnivå - Maisey, George H (Naturen, 1978)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; geologi; havbunnen; topografi

The geology and petrology of Bouvetøya, south Atlantic Ocean - Imsland, Pall; Larsen, Jørgen Gutzon; Prestvik, Tore; Sigmond, Ellen M (Lithos, 1977)
Keywords: Bouvetøya; forskning; geologi; petrologi

Antarktis i fokus - hva gjør norsk forskning? - Orheim, Olav (Forskningsnytt, 1975)
Keywords: Antarktis; NARE ekspedisjoner; geologi; glasiologi; havis; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; polarområdene

Enorme rikdommer skjult i norsk Antarktis? - Fisksdal, Jan (Nå, 1971)
Keywords: Dronning Maud Land; ekspedisjoner; geologi; mineraler; ressurser

Antarktis uten ispanser - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; geofysikk; geologi

Glaciology and glacial geology on Deception Island - Kläy, Jean-Roland; Orheim, Olav (Antarctic Journal of the United States, 1969)
Keywords: Antarktis; geologi; glasiologi

Norwegian Antarctic Expedition, 1968-69 - Winsnes, Thore S. (Antarctic Journal of the United States, 1969)
The aim of the Norwegian Antarctic Expedition was to carry out mapping, geological and glaciological investigations of the Kraul Mts. in western Queen Maud Land. The expedition received the assistance of the National Science Foundation in the provision of American equipment and arrangements for logistics. The six member expedition, equipped for 2 1/2 months of field operations was taken by LC-130 Hercules aircraft from McMurdo to the Kraul Mts. where on several sledge journeys, covering 800 km in all, the geology of the mountains was mapped, triangulations made and base measurements taken during Nov. 22, 1968 to Jan. 20, 1969. The geology of the Kraul Mts. is rather monotonous, consisting of amygdaloid basic-to-intermediate lavas in thick, nearly flat-lying beds. An ultrabasic olivine-rich intrusive is dominant in the westernmost part of the mountains. In the east, a small isolated outcrop con sisted of sedimentary rocks in a sequence of about 50 m, containing a fossil Glossopteris flora of Permian Age. All mountains were crossed by dolerite sills and dykes. During work in the mountains, animal and plant life were observed, and some samples were taken. Core drillings were taken at the ice shelf 70 km to the N, for comparison with main basic cores.
Keywords: Dronning Maud Land; Norwegian Antarctic Expedition 1968-69; geodesi; geologi; glasiologi; kartlegging; topografi

Norsk Polarinstitutts målevirksomhet - Luncke, Bernhard (Norsk tidsskrift for jordskifte og landmåling, 1959)
Keywords: Antarktis; botanikk; ekspedisjoner; forskning; geodesi; geologi; glasiologi; kartlegging; meteorologi; ornitologi; oseanografi; zoologi

A Radar Survey of the Ice Barrier - Higgins, Robert (Journal of Navigation, 1952)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geografi; geologi

An international expedition to Antarctica. The Voyage to Queen Maud Land - Roots, Ernest Frederick (Geographical Magazine, 1950)
Keywords: Antarktis; Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi

Den planerade norsk-svensk-brittiska Antarktis-expeditionen - Ahlmann, Hans Wilhelmsson (Ymer, 1948)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; ekspedisjoner; forskning; geologi; glasiologi; meteorologi

Bouvet-Øen (The Island of Fog) - Petersen, Wilhelm (Naturens Verden, 1930)
Keywords: Bouvetøya; Norvegia ekspedisjonen; geologi; oppdagelsesreiser

Topography of South Victoria Land (Antarctic) - Bernacchi, Louis Charles (The Geographical Journal, 1901)
Keywords: Antarktis; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; geologi; oppdagelsesreiser; topografi

The First Landing On The Antarctic Continent : being An Account of the Recent Voyage Of The Whaler "Antarctic" - Borchgrevink, Carsten Egeberg (The Century illustrated monthly magazine, 1896)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

A Voyage to the Antarctic Sea - Borchgrevink, Carsten Egeberg (Report of the Sixty-Fifth meeting of the British Association for the Advancement of Science helt at Ipswich in September 1895, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The "Antarctic's" Voyage to the Antarctic - Borchgrevink, Carsten Egeberg (The Geographical Journal, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

The Voyage of the “Antarctic” to Victoria Land - Borchgrevink, Carsten Egeberg (Nature, 1895)
Keywords: Antarktis; D/S Antarctic; Kapp Adare; Rosshavet; Victoria Land; botanikk; ekspedisjoner; forskning; første landgang; geologi; hvalfangere; hvalfangst; oppdagelsesreiser; selfangst; zoologi

Begleitworte zur Karte des Dirck Gherritz Archipels - Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; ekspedisjoner; geografi; geologi; oppdagelsesreiser

Kapit. Larsens antarktische Entdeckungen - Petersen, J; Larsen, Carl Anton; Wichmann, Hugo (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Keywords: Antarktis; Carl Anton Larsen; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Die Reisen des "Jason" und der "Hertha" in das Antarktische Meer 1893/94 : und die wissenschaftliche Ergebnisse dieser Reisen - Petersen, Johannes; Friedrichsen, Ludwig (Mitteilungen der Geographischen Gesellschaft in Hamburg, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Hertha (skip); Vestantarktis; dagbok; ekspedisjoner; forskning; geologi; hvalfangere; oppdagelsesreiser

Das Wiedererwachen der antarktischen Forschung - Wichmann, Hugo; [Hassenstein, Bruno] (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1895)
Keywords: Antarktis; Carl Anton Larsen; D/S Antarctic; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Notes on an important geographical discovery in the Antarctic Regions - Murray, John (Scottish Geographical Magazine, 1894)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; Vestantarktis; dagbok; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser

Das neu entdeckte Land im antarktischen Gebiet - Schück, Albert (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1894)
Keywords: Antarktis; Carl Anton Larsen; D/S Jason; dagbøker; ekspedisjoner; forskning; geografi; geologi; hvalfangere; oppdagelsesreiser